Separator for power storage device and method for manufacturing the same
By using resin composition composed of specific resins and crosslinking reaction technology, the performance differences of the partitions for lithium-ion batteries at low temperatures and high temperatures are solved, and the high-temperature film rupture and low-temperature shutdown functions are achieved, thereby improving the output and safety of the battery.
Patent Information
- Application Number
- CN202210864759.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-31
- Filing Date
- 2019-10-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-10-11
AI Technical Summary
The existing lithium-ion battery separators are difficult to take into account the low-temperature shutdown function and high-temperature film rupture, and the circulation characteristics are poor during long-term use, which poses a risk of battery safety.
A microporous film is made of a resin composition with a specific resin composition, and a higher-order structure is constructed through a cross-linking reaction, combined with heat treatment and affinity treatment steps, an oligosiloxane bond is formed, and the heat resistance and film rupture of the separator are improved.
The high-temperature film rupture and low-temperature closing functions of the separator are achieved, the output, circulation characteristics and safety of the lithium-ion battery are improved, and the generation of unmelted resin aggregates are suppressed.
Smart Images

Figure CN115295956B_ABST
Abstract
Description
[0001] This application is a divisional application of an application filed on October 11, 2019, with application number 201980007241X and invention name "Separator for lithium-ion battery". Technical Field
[0002] The present invention relates to a separator for a power storage device and a method for producing the same, and more specifically, to a microporous membrane containing a modified polyolefin suitable for use as a separator for a lithium ion battery and a method for producing the same. Background Art
[0003] Microporous membranes are widely used as separation or selective permeation separation membranes and isolation materials for various substances. Examples of their use include microfiltration membranes, separators for fuel cells and capacitors, or substrates for functional membranes for filling functional materials into pores to exert new functions, separators for batteries, etc. Among them, polyolefin microporous membranes are suitable for use as separators for lithium-ion batteries widely used in notebook personal computers, mobile phones, digital cameras, etc. In order to ensure battery safety, separators are required to take into account both the activation of the shutdown function and the increase in the membrane rupture temperature. For example, Patent Document 1 describes the adjustment of the high-order physical properties of polyolefin resins as an essential component of separators for lithium-ion batteries. In addition, as shown in Patent Document 2, it is known that in a specific crystallinity and gel fraction region, the shutdown function is used to suppress the heat release caused by the short circuit inside the battery, and on the other hand, even if a high temperature portion is locally generated in the battery cell, the membrane will not be broken (breakdown at 170°C or above), thereby ensuring the safety of the battery. More specifically, regarding Patent Documents 1 and 2, it has been experimentally discovered that high-temperature membrane ruptibility can be exhibited by constructing a silane crosslinking portion (gel structure) in a polyolefin separator.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 9-216964
[0007] Patent Document 2: International Publication No. 97 / 44839
[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 11-144700
[0009] Patent Document 4: Japanese Patent Application Laid-Open No. 11-172036
[0010] Patent Document 5: Japanese Patent Application Publication No. 2001-176484
[0011] Patent Document 6: Japanese Patent Application Publication No. 2000-319441
[0012] Patent Document 7: Japanese Patent Application Publication No. 2017-203145
[0013] Patent Document 8: International Publication No. 2010 / 134585
[0014] Patent Document 9: Japanese Patent Application Publication No. 2016-072150
[0015] Patent Document 10: Japanese Patent Application Publication No. 2007-299612 Summary of the invention
[0016] Problem that the invention aims to solve
[0017] In recent years, the high output and high energy density of lithium-ion secondary batteries for mobile devices or vehicles are being developed. On the other hand, the battery cells are required to be miniaturized and have stable cycle discharge and charge performance during long-term use. Therefore, as the separator used, it is necessary to be a thin film (for example, less than 15μm) and a high-quality separator (for example, with uniform physical properties and no resin agglomerates). Furthermore, on the basis of the above performance, the level of battery safety is more stringent than before. As also recorded in Patent Documents 1 and 2, it is required to have a shutdown function and high-temperature film rupture properties, and it is expected to develop a resin composition and a manufacturing method for separators that can be stably produced. In this regard, as the level of the shutdown temperature, the lower the temperature than 150°C, the better. In addition, as the level of the film rupture temperature, the higher the temperature, the better.
[0018] For example, the method described in patent document 3 uses a cross-linking catalyst masterbatch during the extrusion process to perform a cross-linking reaction of silane-modified polyethylene in an extruder, but the generation of resin agglomerates also occurs, which reduces the uniformity of the physical properties of the separator. For this method, the methods described in patent documents 4, 5, and 6 are dealt with by setting a plasticizer extraction process, a silane gel cross-linking process, or controlling the gel fraction of the resin film, or forming the uncross-linked resin by hot water and then dehydrating it. In addition, patent document 7 proposes to provide a heat-resistant resin microporous film, which is excellent in low heat shrinkage, low fluidity and resistance to melting by adjusting the gel fraction, storage modulus, maximum shrinkage based on thermomechanical analysis (TMA) and free radical amount measured by electron spin resonance method (ESR) of a polyolefin microporous film.
[0019] Furthermore, regarding separators for power storage devices, from the perspectives of dimensional stability, maintaining the shutdown function and increasing the membrane rupture temperature, dimensional stability, etc., it is proposed to configure an inorganic porous layer containing inorganic particles such as calcined kaolin and boehmite and a resin binder on the surface of at least one side of a polyolefin microporous membrane (Patent Documents 8 and 9). In addition, for example, a separator is proposed in which the ratio of the thickness of the A layer having the shutdown characteristic to the B layer containing an aramid resin and an inorganic material is adjusted within a prescribed range (Patent Document 10).
[0020] However, the method disclosed in Patent Document 4 does not allow the silane crosslinking reaction to proceed sufficiently, and it is difficult to obtain high-temperature film breakage resistance. The plasticizer extraction steps disclosed in Patent Documents 3 and 4 use a tin (II)-based crosslinking catalyst, which allows the crosslinking reaction to proceed, but there is a risk that the crosslinking catalyst will remain.
[0021] The heat-resistant resin microporous membrane described in Patent Document 7 is obtained by coating a film made porous by a dry method with a photopolymerizable coating liquid. In addition, in Example 5 of Patent Document 7, a low molecular weight silane coupling agent such as γ-methacryloxypropyltrimethoxysilane is added to the porous membrane. However, if a low molecular weight silane coupling agent is used in a wet porous method, it is expected that the low molecular weight silane coupling agent is likely to react or bond with a plasticizer used for porosification, rather than bonding with the resin of the porous membrane.
[0022] In addition, the coating layer recorded in patent document 7 is formed by a cross-linking reaction by applying a compound with a polymerizable functional group to a resin porous film, so it is expected that a portion of the liquid immersion to the resin porous film will occur while the coating layer is applied, and after the cross-linking reaction is carried out, it is expected that a mixed region of them will be formed near the interface between the coating layer and the resin porous film. Thus, good TMA thermal shrinkage performance can be obtained, but the reduction of the battery cycle characteristics caused by the blockage of the resin porous film or the reduction of the fuse (shutdown) performance caused by the melting phenomenon of the resin porous film can be expected. Furthermore, in the composite microporous film obtained by the method recorded in patent document 7, a small amount of free radical species compounds are detected by ESR. Due to the residue, when the composite microporous film is assembled into the battery, free radical reactions are carried out with other components, especially with the electrolyte, and a chain reaction of decomposing the electrolyte can be expected, which is considered to significantly deteriorate the battery performance.
[0023] Furthermore, the battery using separators as described in Patent Documents 3 to 7 has poor cycle characteristics, and in addition, unpredictable side reactions may be induced in the battery during long-term use, which may reduce the battery safety. In addition, in order to obtain the shutdown function and high-temperature film breaking properties, as shown above, the silane crosslinking method has problems, and the porous structure that is most important for the separator cannot be constructed by only silane grafted polyolefins, so the development of resin mixed compositions is also indispensable.
[0024] Furthermore, the microporous membranes and separators recorded in patent documents 1, 2, and 7 lack research on inorganic porous layers containing inorganic particles and resin binders configured on their surfaces. The existing separators with inorganic porous layers on microporous membranes appear to have increased film breaking temperatures on the temperature-resistance curve of the storage device. However, in fact, sometimes resins dissolve from the microporous membrane into the inorganic porous layer, so it is expected that the membrane as a whole of the separator will be reduced and the resulting reduction in stress tolerance. Therefore, although the multilayer porous membranes recorded in patent documents 8 and 9 have polyolefin microporous membranes and inorganic porous layers, there is room for research on both the low-temperature shutdown function and high-temperature film breaking properties of separators for storage devices, or improving the cycle characteristics of storage devices and battery nail puncture safety.
[0025] Furthermore, the separators for power storage devices described in Patent Documents 1, 2, and 10 still have room for improvement in terms of achieving improved performance of the power storage devices.
[0026] In view of the above problems, an object of the present invention is to provide a separator and a method for producing the separator that can achieve both shutdown function and high-temperature film rupture properties and improve the output, cycle characteristics and / or safety of a power storage device.
[0027] Solutions for solving problems
[0028] The inventors of the present invention have conducted extensive research to solve the above problems and have found that the above problems can be solved by using a resin composition having a specific resin composition to complete the process of constructing a high-order structure of a microporous membrane and then performing a crosslinking reaction (gelation) under specific conditions, thereby completing the present invention. That is, the present invention is as follows. [1]
[0030] A method for manufacturing a separator for an electrical storage device, comprising the following steps:
[0031] (1) a sheet forming step, in which the silane grafted modified polyolefin, polyethylene and plasticizer are extruded into a sheet by an extruder, cooled and solidified, and processed into a sheet-shaped body;
[0032] (2) a stretching step of biaxially stretching the sheet-like formed body at a surface ratio of 20 to 250 times to form a stretched product;
[0033] (3) a porous body forming step of extracting the plasticizer from the stretched product to form a porous body;
[0034] (4) a heat treatment step of subjecting the porous body to heat treatment, stretching and relaxing the porous body in the width direction, and obtaining a heat-treated porous body;
[0035] (5) an affinity treatment step of immersing the heat-treated porous body in an organic solvent having amphiphilicity to water and organic matter to increase the affinity of the heat-treated porous body to the liquid, thereby obtaining an affinity-treated porous body having the organic solvent immersed therein;
[0036] (6) a cross-linking treatment step, wherein the affinity-treated porous body is contacted with a mixture containing an organic metal catalyst and water, or the affinity-treated porous body is immersed in an alkaline solution or an acid solution to perform a silane dehydration condensation reaction to form oligosiloxane bonds to obtain a cross-linked porous body; and
[0037] (7) A water washing and drying step of washing and drying the cross-linked porous body. [2]
[0039] The method for producing a separator for a power storage device according to item 1, wherein a mass ratio of the silane graft-modified polyolefin to the polyethylene (mass of the silane graft-modified polyolefin / mass of the polyethylene) is 0.05 / 0.95 to 0.40 / 0.60. [3]
[0041] The method for producing a separator for an electric storage device according to item 1 or 2, wherein the separator for an electric storage device comprises a microporous film having a melting and rupture temperature of 180° C. to 220° C. as measured by thermomechanical analysis (TMA). [4]
[0043] The method for producing a separator for a power storage device according to any one of items 1 to 3, wherein in the cross-linking treatment step, the affinity-treated porous body is immersed in the alkaline solution or the acid solution. [5]
[0045] According to the method for producing a separator for a power storage device as described in item 4, in the cross-linking treatment step, the affinity-treated porous body is immersed in the alkaline solution. [6]
[0047] The method for producing a separator for a power storage device according to item 5, wherein the alkaline solution has a temperature of 20°C to 100°C and a pH of 8 to 14. [7]
[0049] According to the method for producing a separator for a power storage device as described in item 4, in the cross-linking treatment step, the affinity-treated porous body is immersed in the acid solution. [8]
[0051] The method for producing a separator for a power storage device according to any one of items 1 to 7, wherein the metal of the organic metal catalyst is at least one selected from the group consisting of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel and lead. [9]
[0053] The method for producing a separator for an electrical storage device according to any one of items 1 to 8, wherein the content of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel or lead in the separator for an electrical storage device is 0.10 ppm or more and 200 ppm or less in total amount in terms of atoms.
[10]
[0055] The method for producing a separator for a power storage device according to any one of items 1 to 9, wherein the silane-grafted modified polyolefin is not a master batch resin containing a dehydration condensation catalyst for cross-linking the silane-grafted modified polyolefin before the sheet forming step.
[11]
[0057] The method for producing a separator for a power storage device according to any one of items 1 to 10, wherein in the water washing and drying step, the cross-linked porous body is washed and dried with water at a temperature of 20 to 100° C. and a pH of 6 to 8.
[12]
[0059] A method for manufacturing an electric storage device, comprising the following steps:
[0060] A step of laminating and / or winding a positive electrode, a separator for a storage device obtained by the method for producing a separator for a storage device according to any one of items 1 to 11, and a negative electrode to obtain a laminate or a wound body;
[0061] The step of placing the aforementioned laminate or wound body into an outer shell;
[0062] A step of injecting electrolyte into the outer shell; and
[0063] A step of connecting lead terminals to the positive electrode and the negative electrode.
[13]
[0065] A method for manufacturing an electricity storage device according to item 12, wherein the electrolyte solution contains an electrolyte containing LiPF6 or other lithium salt electrolyte containing fluorine (F).
[14]
[0067] A separator for an electric storage device comprises a microporous membrane comprising a silane-modified polyolefin and polyethylene, wherein the microporous membrane has a melting and rupture temperature of 180° C. to 220° C. as measured by thermomechanical analysis (TMA).
[15]
[0069] The separator for an electrical storage device according to item 14, wherein the separator for an electrical storage device contains 0.10 ppm to 200 ppm of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel or lead in a total amount converted into atoms.
[16]
[0071] The separator for an electric storage device according to item 14 or 15, wherein the separator for an electric storage device contains zinc or tin in an atomically converted total amount of 0.10 ppm to 200 ppm.
[17]
[0073] The separator for a power storage device according to any one of items 14 to 16, comprising:
[0074] The aforementioned microporous membrane, and
[0075] An inorganic porous layer including inorganic particles and a resin binder is disposed on at least one surface of the microporous membrane.
[18]
[0077] The separator for a power storage device according to item 17, wherein the content of the inorganic particles in the inorganic porous layer is 5% by mass to 99% by mass.
[19]
[0079] The separator for a power storage device according to item 17 or 18, wherein the content of the silane-modified polyolefin in the microporous film is 0.5% by mass to 40% by mass.
[20]
[0081] A separator for a storage battery device according to any one of items 17 to 19, wherein the inorganic particles are at least one selected from the group consisting of aluminum oxide (Al2O3), silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, cerium oxide, yttrium oxide, zinc oxide, iron oxide, silicon nitride, titanium nitride, boron nitride, silicon carbide, aluminum hydroxide (AlO(OH)), talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, diatomaceous earth, quartz sand and glass fiber. [twenty one]
[0083] The separator for a power storage device according to any one of items 17 to 20, wherein the glass transition temperature (Tg) of the resin binder is -50°C to 100°C. [twenty two]
[0085] A separator for a power storage device, comprising a first porous layer (layer A) containing a silane-modified polyolefin and having a cross-linked structure, and a second porous layer (layer B) containing inorganic particles.
[0086] The ratio (TA / TB) of the thickness (TA) of the A layer to the thickness (TB) of the B layer is 0.22 or more and 14 or less. [twenty three]
[0088] The separator for a power storage device according to Item 22, wherein the film rupture temperature of the A layer measured by thermomechanical analysis (TMA) is 180° C. or higher and 220° C. or lower. [twenty four]
[0090] The separator for a power storage device according to item 22 or 23, wherein a total thickness (TA+TB) of the A layer and the B layer is 3.0 μm or more and 22 μm or less.
[25]
[0092] The separator for a power storage device according to any one of items 22 to 24, wherein the amount of the inorganic particles in the layer B is 20 mass % or more and 99.5 mass % or less based on the total amount of the layer B.
[26]
[0094] The separator for a power storage device according to any one of items 22 to 25, wherein the layer B contains a resin binder.
[27]
[0096] The separator for a power storage device according to any one of items 22 to 26, wherein the layer A further contains polyethylene as a polyolefin different from the silane-modified polyolefin.
[28]
[0098] The separator for a power storage device according to any one of items 22 to 27, wherein the amount of the silane-modified polyolefin in the layer A is 3% by mass or more based on the total amount of the layer A.
[29]
[0100] A separator for an electric storage device having a shutdown temperature of 130° C. to 160° C. measured based on resistance under a pressure of 10.0 MPa and a melting temperature of 200° C. or more.
[30]
[0102] A method for producing a separator for an electric storage device, which is the method for producing a separator for an electric storage device according to any one of items 14 to 29, comprising the following steps:
[0103] (1) a sheet forming step, in which the silane grafted modified polyolefin, polyethylene and plasticizer are extruded into a sheet by an extruder, cooled and solidified, and processed into a sheet-shaped body;
[0104] (2) a stretching step of biaxially stretching the sheet-like formed body at a surface ratio of 20 to 250 times to form a stretched product;
[0105] (3) a porous body forming step of extracting the plasticizer from the stretched product to form a porous body;
[0106] (4) a heat treatment step of subjecting the porous body to heat treatment, stretching and relaxing the porous body in the width direction, and obtaining a heat-treated porous body;
[0107] (5) an affinity treatment step of immersing the heat-treated porous body in an organic solvent having amphiphilicity to water and organic matter to increase the affinity of the heat-treated porous body to the liquid, thereby obtaining an affinity-treated porous body having the organic solvent immersed therein;
[0108] (6) a cross-linking treatment step, wherein the affinity-treated porous body is contacted with a mixture containing an organic metal catalyst and water, or the affinity-treated porous body is immersed in an alkaline solution or an acid solution to perform a silane dehydration condensation reaction to form oligosiloxane bonds, thereby obtaining a cross-linked porous body;
[0109] (7) a water washing and drying step of washing and drying the cross-linked porous body to obtain a microporous membrane comprising the silane-modified polyolefin; and
[0110] (8A) A coating step of forming an inorganic porous layer containing inorganic particles and a resin binder on at least one surface of the microporous membrane.
[31]
[0112] An electricity storage device comprising an electrode, the separator for an electricity storage device according to any one of items 14 to 29, and a nonaqueous electrolyte.
[0113] Effects of the Invention
[0114] According to the present invention, the shutdown function and high-temperature film rupture properties of a separator for a storage device can be taken into account, thereby improving the output, cycle characteristics and / or safety of the storage device, and / or suppressing the generation of unmelted resin agglomerates in the manufacturing process of the separator for the storage device, or ensuring high temperature and high pressure tolerance. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 This is a TMA chart of the separator obtained in Example I-1.
[0116] Figure 2 This is a graph showing heat generation during a nail penetration safety test of a battery using the separator obtained in Example I-1.
[0117] Figure 3 This is a graph showing a voltage drop during a nail penetration safety test of a battery using the separator obtained in Example I-1.
[0118] Figure 4 Silane-modified polyolefin raw material 1 obtained using polyolefin 1 H-NMR spectra (a) and 13 C-NMR spectrum (b).
[0119] Figure 5 Silane-modified polyolefin raw material 2 obtained using polyolefin 1 H-NMR spectra (a) and 13 C-NMR spectrum (b).
[0120] Figure 6 is used Figure 4 The separator made of the silane-modified polyolefin raw material 1 before crosslinking is shown in FIG. 1 H-NMR spectra (a) and 13 C-NMR spectrum (b). DETAILED DESCRIPTION
[0121] Hereinafter, embodiments of the present invention will be described. The present invention is not limited to the embodiments described below, and various modifications can be made within the scope of the gist of the present invention.
[0122] In this specification, "~" refers to the numerical value including both ends as the upper limit and the lower limit. In addition, in this specification, the upper limit and the lower limit of the numerical range can be combined arbitrarily. For example, the upper limit of the preferred numerical range can be combined with the lower limit of the more preferred numerical range, and vice versa, the upper limit of the more preferred numerical range can also be combined with the lower limit of the preferred numerical range.
[0123] It should be noted that, in this specification, "on" and "formed on the surface of" do not mean that the positional relationship of each component is limited to "directly above". For example, "layer B formed on layer A" and "layer B formed on the surface of layer A" do not exclude the inclusion of an arbitrary layer between layer A and layer B that does not belong to either layer.
[0124] The properties of only the microporous membrane described below can be measured by removing layers other than the microporous membrane (for example, an inorganic porous layer) from the separator for a power storage device.
[0125] <Separator for power storage device>
[0126] One embodiment of the present invention is a separator for a power storage device (hereinafter also referred to as a "separator"). Since the separator needs to have insulation and ion permeability, it generally includes paper, polyolefin nonwoven fabric, or resin microporous membrane as an insulating material having a porous structure. In particular, in lithium-ion batteries, polyolefin microporous membranes that can construct a separator with resistance to redox degradation and a dense and uniform porous structure are preferred.
[0127] Here, the microporous membrane refers to a membrane (thin film) formed of a porous body, and the average pore diameter thereof is preferably 10 nm to 500 nm, and more preferably 30 nm to 100 nm.
[0128] When the power storage device includes a separator, the separator may be removed from the power storage device.
[0129] <First Embodiment>
[0130] The separator of the first embodiment of the present invention comprises a microporous membrane having a melting and rupture temperature of 180°C to 220°C measured by thermomechanical analysis (TMA), and the microporous membrane comprises silane-modified polyolefin and silane-unmodified polyethylene. From the perspective of high-temperature rupture resistance and the safety of the power storage device, the microporous membrane has a melting and rupture temperature of 180°C to 220°C, preferably 180°C to 200°C, when measured by thermomechanical analysis (TMA). Even if the power storage device is abnormally exothermic due to an unexpected runaway reaction, it is expected that the movement of ions and the discharge inside or outside the power storage device accompanying it will be stopped by the shutdown function of the separator. Then, it is expected that the power storage device will be cooled as a whole by a refrigerant to ensure safety. On the other hand, if the rupture temperature of the microporous membrane is within the above-mentioned numerical range, even if the power storage device as a whole is not fully cooled, and in the event of reaching an ultra-high temperature region, the separator can also melt and rupture, penetrate into the two electrodes, and apply active materials, thereby easily suppressing further heat release. The membrane rupture temperature of the microporous membrane can be measured by the method described in the Examples section, and can also be controlled by changing the stretching temperature and / or stretching ratio in the production process.
[0131] From the perspective of its manufacturing process and the perspective of ensuring safety by controlling the amorphous part of the microporous membrane, the separator of the first embodiment preferably controls the content of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel or lead in the range of more than 0.10 ppm and less than 200 ppm in terms of total atomic content, more preferably controls the content of zinc or tin in the range of more than 0.10 ppm and less than 200 ppm in terms of total atomic content, and further preferably controls it in the range of more than 1 ppm and less than 150 ppm.
[0132] The separator of the first embodiment may include: a microporous membrane; and an inorganic porous layer including inorganic particles and a resin binder disposed on at least one side of the microporous membrane, from the perspective of taking into account the shutdown function at a relatively low temperature and the film breakability at a relatively high temperature and improving the cycle characteristics and safety of the power storage device. The separator may be a state in which the microporous membrane is used as a substrate and the substrate is composited with an inorganic coating layer.
[0133] <Second Embodiment>
[0134] The separator of the second embodiment of the present invention comprises a first porous layer (A layer) comprising a silane-modified polyolefin and having a cross-linked structure and a second porous layer (B layer) comprising inorganic particles. The A layer and the B layer are each a single layer or multiple layers. The B layer is formed only on one side of the A layer or on both sides.
[0135] In LIB, a representative example of a power storage device, lithium (Li) ions move back and forth between the positive and negative electrodes. Therefore, by arranging a separator including layer A and layer B between the positive and negative electrodes, the Li ions can move between the positive and negative electrodes at a relatively high speed while avoiding contact between the positive and negative electrodes.
[0136] (Thickness ratio)
[0137] The A layer functions as a cross-linked microporous membrane, and the B layer functions as an inorganic porous layer formed on the microporous membrane.
[0138] Here, the ratio (TA / TB) of the thickness (TA) of the A layer to the thickness (TB) of the B layer is 0.22 or more and 14 or less. If the ratio (TA / TB) is 0.22 or more, the existence ratio of the A layer in the separator can be sufficiently ensured, and the function of the A layer can be exerted. On the other hand, if the ratio (TA / TB) is 14 or less, the existence ratio of the B layer in the separator can be sufficiently ensured, and the function of the B layer can be exerted.
[0139] By making the A layer and the B layer have specific structures, and further setting the ratio (TA / TB) to the above range, a separator capable of improving the cycle characteristics and safety of the power storage device can be provided. Such a separator can be suitably used as a constituent material of a LIB for mobile device mounting or vehicle mounting, for example.
[0140] From the viewpoint of the above-mentioned effects, the ratio (TA / TB) is preferably 0.8 or more, and more preferably 1.0 or more. On the other hand, the ratio (TA / TB) is preferably 5.5 or less, and more preferably 3.2 or less.
[0141] The ratio (TA / TB) can be set to, for example, less than 2.5, less than 2.0, or less than 1.0. In this case, the thickness (TA) of layer A is less than 2.5 times or less than the thickness (TB) of layer B relative to the thickness (TB) of layer B, making it easy to achieve thin filming of layer A or even thin filming of the separator.
[0142] The total thickness (TA+TB) of the A layer and the B layer is preferably 3.0 μm or more and 22 μm or less. If the total thickness (TA+TB) is 3.0 μm or more, the membrane strength of the separator tends to be improved. On the other hand, if the total thickness (TA+TB) is 22 μm or less, the ion permeability of the separator tends to be improved.
[0143] From the viewpoint of the above-mentioned effects, the total thickness (TA+TB) is more preferably 3.5 μm or more, and further preferably 4.0 μm or more. On the other hand, the total thickness (TA+TB) is more preferably 20 μm or less, and further preferably 18 μm or less.
[0144] The total thickness (TA+TB) can be set to, for example, less than 11 μm, 10 μm or less, or 8 μm or less. Even such a thin separator can improve the cycle characteristics and safety of the power storage device as long as it is within the scope of the present invention.
[0145] The ratio (TA / TB) and the total thickness (TA+TB) can be measured by the methods described in the Examples section, and can be controlled by adjusting the thickness (TA) and / or the thickness (TB). The A layer and the B layer will be described later.
[0146] (Shutdown temperature and melting temperature)
[0147] Regarding layer A, it is preferred that the shutdown temperature (sometimes called the melting temperature) measured based on resistance under a pressure of more than 0.1 MPa and less than 10.0 MPa (preferably under a pressure of 10 MPa) is 130°C to 160°C and the melting temperature (sometimes called the film rupture temperature) is more than 200°C.
[0148] If the shutdown temperature is 130°C or higher, unnecessary shutdown function can be avoided during normal reaction of the power storage device, and sufficient output characteristics of the power storage device can be ensured. On the other hand, if the shutdown temperature is 160°C or lower, the shutdown function can be appropriately exerted during abnormal reaction of the power storage device.
[0149] Furthermore, if the melting temperature is 200° C. or higher, the abnormal reaction of the power storage device can be stopped before reaching the ultrahigh temperature region, and the separator can be prevented from melting and breaking during the abnormal reaction of the power storage device.
[0150] That is, by making the shutdown temperature and the melting temperature satisfy the above conditions, a separator that can provide a power storage device with excellent heat resistance, closed-cell characteristics (shutdown function), and melt-break film characteristics (melting function) can be realized, and the separator itself can also ensure mechanical characteristics, ion permeability, etc. Therefore, by having a separator whose shutdown temperature and melting temperature satisfy the above conditions, the power storage device can achieve improved cycle characteristics and safety.
[0151] From the viewpoint of the above effects, the shutdown temperature is preferably higher than 130°C, more preferably 135°C or higher, and further preferably 136°C or higher. On the other hand, the shutdown temperature is preferably 150°C or lower, more preferably 148°C or lower, and further preferably 146°C or lower.
[0152] Likewise, from the viewpoint of the above-mentioned effects, the melting temperature is preferably 175°C or higher, more preferably 178°C or higher, and further preferably 180°C or higher. On the other hand, the melting temperature is preferably 230°C or lower, more preferably 225°C or lower, and further preferably 220°C or lower.
[0153] Even if the melting temperature cannot be accurately measured in a range exceeding 200° C., the above-mentioned condition “the melting temperature is 200° C. or higher” is satisfied as long as the temperature is 200° C. or higher.
[0154] The "shutdown temperature" and "melting temperature" in this specification refer to the values obtained when the resistance is measured under the above-mentioned pressure. That is, while applying the above-mentioned pressure to the stack including the positive electrode, the separator and the negative electrode, the temperature of the stack is increased, and the shutdown temperature and the melting temperature are derived based on the AC resistance (AC resistance between electrodes) that increases accordingly. In the second embodiment, the temperature when the AC resistance exceeds the prescribed reference value (for example, 1000Ω) for the first time is set as the shutdown temperature, and the temperature when the AC resistance exceeding the above-mentioned reference value is further heated and drops below the above-mentioned reference value (for example, 1000Ω) is set as the melting temperature.
[0155] The stack can be pressurized using a hydraulic jack, but is not limited thereto, and known pressurization means other than the hydraulic jack can be used. In addition, the stack can be heated using an aluminum heater, but is not limited thereto, and known heating means other than the aluminum heater can be used.
[0156] The shutdown temperature and the melting temperature can be measured by the method described in the Examples section, and can also be controlled by adjusting the composition of the A layer or the production method.
[0157] (Heat shrinkage at 150°C)
[0158] In layer A, the heat shrinkage rate (T2) at 150°C after forming its cross-linked structure is preferably 0.02 times or more and 0.91 times or less of the heat shrinkage rate (T1) at 150°C before forming the cross-linked structure. In other words, the ratio (T2 / T1) of the heat shrinkage rate (T2) at 150°C after forming the cross-linked structure to the heat shrinkage rate (T1) at 150°C before forming the cross-linked structure is preferably 0.02 or more and 0.91 or less. As the heat shrinkage rate here, the larger value of the heat shrinkage rate of layer A in the machine direction (MD) and the heat shrinkage rate of layer A in the width direction (TD) is used.
[0159] Since the A layer can form a cross-linked structure based on silane-modified polyolefin, the change in its thermal shrinkage before and after cross-linking can be focused on.
[0160] If the ratio (T2 / T1) is 0.02 or more, the occurrence of short circuit can be effectively suppressed, thereby reliably preventing the temperature rise of the entire power storage device and the smoke and fire that may be generated therefrom. On the other hand, if the ratio (T2 / T1) is 0.91 or less, it can be judged that the crosslinking reaction in the A layer is successfully and fully carried out. That is, if the ratio (T2 / T1) is within the above range, a separator for a power storage device that can improve the cycle characteristics and safety of the power storage device can be provided.
[0161] Therefore, from the viewpoint of the above-mentioned effect, the ratio (T2 / T1) is preferably 0.03 or more, more preferably 0.05 or more, and further preferably 0.07 or more. On the other hand, the ratio (T2 / T1) is preferably 0.7 or less, more preferably 0.5 or less, and further preferably 0.4 or less.
[0162] The heat shrinkage ratio (T1) at 150° C. before forming a cross-linked structure is preferably 70% or less, more preferably 60% or less.
[0163] In addition, the heat shrinkage rate (T2) at 150°C after forming the cross-linked structure is preferably 60% or less, and more preferably 50% or less. By forming a cross-linked structure, there is a tendency for the above heat shrinkage rate to decrease compared to before forming the cross-linked structure, so the heat shrinkage rate (T2) is generally a value smaller than the heat shrinkage rate (T1).
[0164] The heat shrinkage at 150° C. can be measured by the method described in the Examples section, and can also be controlled by adjusting the structure of the A layer or the production method.
[0165] The separators of the first and second embodiments may be interchangeable or may be combined with each other. The separators of the first and second embodiments may include layers other than the microporous membrane and the inorganic porous layer as desired. The constituent elements of the separators of the first and second embodiments are described below.
[0166] [Microporous membrane]
[0167] The microporous membrane can be formed of polyolefin or modified polyolefin.
[0168] The microporous membrane contains silane-modified polyolefin and may contain other polyolefins as desired. The microporous membrane can undergo a crosslinking reaction during the manufacturing process of the separator due to the silane crosslinking property of the silane-modified polyolefin.
[0169] As the polyolefin contained in the microporous membrane, there is no particular limitation, and for example, homopolymers of ethylene or propylene or copolymers formed by at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene and norbornene can be cited. Among these, from the perspective of being able to perform heat setting (sometimes abbreviated as "HS") at a higher temperature without clogging the pores, high-density polyethylene (homopolymer) or low-density polyethylene is preferred, and high-density polyethylene (homopolymer) is more preferred. It should be noted that the polyolefin can be used alone or in combination of two or more.
[0170] The microporous membrane is preferably manufactured using both silane-modified polyolefin and ultra-high molecular weight polyethylene (UHMWPE) as raw materials from the perspective of resistance to redox degradation and a dense and uniform porous structure. Generally, the weight average molecular weight of ultra-high molecular weight polyethylene (UHMWPE) is known to be 1,000,000 or more. More preferably, in the manufacture of the microporous membrane or separator, the weight ratio of silane-modified polyolefin to UHMWPE (silane-modified polyolefin weight / UHMWPE weight) is 0.05 / 0.95 to 0.40 / 0.60.
[0171] The content of polyolefin contained in the microporous membrane is preferably 50% by weight or more and 100% by weight or less, preferably 70% by weight or more and 100% by weight or less, preferably 80% by weight or more and 100% by weight or less. In addition, the microporous membrane preferably contains a polyolefin having a weight average molecular weight of 100,000 or more and less than 1,000,000 (relative to the whole polyolefin, preferably 40% by weight or more, more preferably 80% by weight or more). The weight average molecular weight of the polyolefin is more preferably 120,000 or more and less than 950,000, and further preferably 130,000 or more and less than 930,000. By using a polyolefin having a weight average molecular weight of 100,000 or more and less than 1,000,000, there is a tendency to relax the shrinkage of the polymer in the early stage in the heating test of the storage device, especially in the heating safety test, which is easy to maintain safety. By adjusting the weight average molecular weight of the microporous membrane to less than 1,000,000, poor forming (membrane texture) during extrusion, which is called melt fracture, can be suppressed. On the other hand, by adjusting the weight average molecular weight of the microporous membrane to more than 100,000, the transfer of depressions when the microporous membrane is wound on a core (winding core) can be suppressed.
[0172] The viscosity average molecular weight of the microporous membrane when the inorganic porous layer is removed and the crosslinking treatment is not performed is preferably 100,000 to 1,200,000, more preferably 150,000 to 800,000, from the viewpoint of preventing the generation of polymer powder due to friction shear during the roll conveyance of the separator.
[0173] The film thickness of the microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, and further preferably 3.0 μm or more, 4.0 μm or more, or 4.5 μm or more. By making the film thickness of the microporous membrane 1.0 μm or more, there is a tendency for the film strength to be further improved. In addition, the film thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less, 22 μm or less, or 19 μm or less. By making the film thickness of the microporous membrane 500 μm or less, there is a tendency for the ion permeability to be further improved. The film thickness of the microporous membrane can be measured by the method described in the examples.
[0174] [First porous layer (layer A)]
[0175] The A layer contains a silane-modified polyolefin and has a cross-linked structure. From the perspective of ensuring oxidation-reduction resistance and a dense and uniform porous structure, the A layer preferably further contains polyethylene as a polyolefin different from the silane-modified polyolefin. It should be noted that the A layer may contain components other than the silane-modified polyolefin and the polyethylene.
[0176] As polyolefins constituting the silane-modified polyolefin in layer A, homopolymers of ethylene or propylene can be cited; copolymers formed by at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene and norbornene, etc. Among them, as polyolefins, from the perspective of being able to perform heat setting at a higher temperature while avoiding clogging of the pores, homopolymers of ethylene (polyethylene) are preferred, high-density polyethylene and / or low-density polyethylene are more preferred, and high-density polyethylene is further preferred. One polyolefin can be used alone or two or more polyolefins can be used in combination.
[0177] The layer A may contain a polymer (other polymer) that is neither silane-modified polyolefin nor polyethylene, within a range that does not excessively impair the effects of the present invention.
[0178] The weight average molecular weight of the entire A layer is preferably 100,000 or more and 1,200,000 or less, and more preferably 150,000 or more and 800,000 or less.
[0179] (Thickness of layer A)
[0180] The thickness (TA) of layer A is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more. If the thickness (TA) is 1 μm or more, there is a tendency for the membrane strength to be further improved. On the other hand, the thickness (TA) is preferably 500 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less. If the thickness (TA) is 500 μm or less, there is a tendency for the ion permeability to be further improved. It should be noted that the thickness (TA) can be set to, for example, 1.00 μm or more, 2.00 μm or more, or 3.00 μm or more.
[0181] In the case where the separator is a separator for LIB, the thickness (TA) is preferably less than 22 μm, more preferably less than 21 μm, and further preferably less than 20.5 μm. In the case where the separator is a separator for LIB, the upper limit of the thickness (TA) can be set to less than 13 μm or less than 8.5 μm. If the thickness (TA) is less than 25 μm, there is a tendency for the permeability to be further improved. It should be noted that the thickness (TA) can be set to, for example, less than 22.00 μm, less than 21.00 μm, less than 20.00 μm, less than 13.00 μm or less than 8.50. The lower limit of the thickness (TA) can be the same as above.
[0182] The thickness (TA) can be measured by the method described in the Examples section, and can also be controlled by changing the stretching ratio of the A layer and the like.
[0183] When the A layer is a single layer, the thickness of the A layer is regarded as the thickness (TA). When the A layer is a plurality of layers, the total thickness of the plurality of A layers is regarded as the thickness (TA).
[0184] The film rupture temperature of layer A measured by thermomechanical analysis (TMA) is preferably above 180°C and below 220°C. Even if the storage device releases heat abnormally due to an unexpected runaway reaction, it is expected that the movement of Li ions and the discharge inside or outside the storage device associated therewith will be stopped by the shutdown function of the separator. Then, it is expected that the entire storage device will be cooled by a refrigerant to ensure safety. On the other hand, by making the film rupture temperature of layer A within the above range, even if the storage device as a whole is not sufficiently cooled, and in the event that it reaches an ultra-high temperature area, the separator can be melted and ruptured, and the active material can be coated on the two electrodes, thereby easily suppressing further heat release.
[0185] The film rupture temperature of the A layer can be measured by the method described in the Examples section, and can also be controlled by changing the stretching temperature and / or stretching ratio of the A layer.
[0186] [Porosity of microporous membrane or layer A]
[0187] The porosity of the microporous membrane or layer A is preferably 20% or more, more preferably 25% or more, and further preferably 28% or more, 30% or more, 32% or more, or 35% or more. If the porosity is 20% or more, there is a tendency for the rapid movement of Li ions to be further improved. On the other hand, the porosity is preferably 90% or less, more preferably 80% or less, and further preferably 60% or less. If the porosity is 90% or less, there is a tendency for the membrane strength to be further improved and the self-discharge to be further suppressed. The porosity can be measured by the method described in the Example column, and can also be controlled in the manufacturing process by changing the stretching temperature and / or the stretching ratio.
[0188] [Air permeability of microporous membrane or layer A]
[0189] The air permeability of the microporous membrane or layer A is preferably 1 sec / 100 cm 3 More preferably, 50 seconds / 100 cm 3 More preferably, 55 seconds / 100 cm 3 If the air permeability is 1 second / 100cm 3 On the other hand, the air permeability is preferably 400 sec / 100 cm 3 Less than 300 seconds / 100 cm 3, more preferably 270 sec / 100 cm 3 If the air permeability is 400 seconds / 100cm 3 The ion permeability tends to be further improved as the air permeability increases. The air permeability can be measured by the method described in the Examples section, and can be controlled by changing the stretching temperature and / or stretching ratio in the production process.
[0190] [Puncture strength of microporous membrane or A layer]
[0191] As the puncture strength of the microporous membrane or the A layer, it is preferably 200gf / 20μm or more, and more preferably 300gf / 20μm or more. If the puncture strength is 200gf / 20μm or more, even if the active material falls off when the separator and the stack of electrodes are wound, it is easy to suppress the film breakage caused by the falling active material. In addition, it is easy to reduce the possibility of short circuit due to the expansion and contraction of the electrode accompanying charging and discharging. On the other hand, the puncture strength is preferably 4000gf / 20μm or less, and more preferably 3800gf / 20μm or less. If the puncture strength is 3500gf / 20μm or less, it is easy to reduce thermal shrinkage during heating. The puncture strength can be measured by the method described in the Example column, and can be controlled by changes in the stretching temperature and / or stretching ratio in the manufacturing process.
[0192] [Tensile strength of microporous membrane or layer A]
[0193] The tensile strength of the microporous film or layer A is preferably 1000 kgf / cm in both MD (the longitudinal direction of the film or layer A, the machine direction or the processing direction) and TD (the direction perpendicular to MD, the width direction of the film or layer A). 2 More preferably 1050kgf / cm 2 More preferably, 1100 kgf / cm 2 By making the tensile strength 1000kgf / cm 2 As described above, there is a tendency that the breakage during slitting or winding of the power storage device is further suppressed, and the short circuit caused by foreign matter in the power storage device is further suppressed. On the other hand, the tensile strength of the microporous membrane or the A layer is preferably 5000 kgf / cm 2 Below, more preferably 4500kgf / cm 2 Below, more preferably 4000kgf / cm 2 Below. If the tensile strength is 5000kgf / cm 2 Then, during the heating test, the microporous film or the A layer relaxes early and the shrinkage force decreases, resulting in a tendency for the safety to be improved.
[0194] [Tensile modulus of microporous membrane or layer A]
[0195] The tensile modulus of the microporous film or A layer is preferably less than 120N / cm in both directions of MD and TD, more preferably less than 100N / cm, and further preferably less than 90N / cm. The tensile modulus of less than 120N / cm indicates that the separator for lithium-ion secondary batteries is not extremely oriented. In heating tests, for example, when a blocking agent such as polyethylene melts and shrinks, stress relaxation occurs in early polyethylene, so that the shrinkage of the separator in the battery is suppressed and the short circuit between the electrodes is easily prevented (i.e., the safety of the separator during heating can be improved). This low tensile modulus is easily achieved by including polyethylene having a weight-average molecular weight of less than 500,000 in the polyolefin forming the microporous film or A layer. On the other hand, the lower limit of the tensile modulus is preferably more than 10N / cm, more preferably more than 30N / cm, and more preferably more than 50N / cm. The tensile modulus can be appropriately adjusted by adjusting the degree of stretching in the manufacturing process or relaxing after stretching as needed.
[0196] <Silane-modified polyolefin>
[0197] The silane-modified polyolefin has a structure in which the main chain is a polyolefin and an alkoxysilyl group is grafted onto the main chain. The silane-modified polyolefin can be obtained by grafting an alkoxysilyl group onto the main chain of a silane-unmodified polyolefin.
[0198] It is presumed that the alkoxysilyl group is converted into a silanol group by a hydrolysis reaction based on water, and a cross-linking reaction occurs to form a siloxane bond (see the following formula; the ratio of the T1 structure, the T2 structure, and the T3 structure is arbitrary). As the alkoxide replaced by the alkoxysilyl group, methoxide, ethoxide, butoxide, etc. can be listed. In the following formula, as R, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, etc. can be listed.
[0199]
[0200] The main chain and the graft are connected by covalent bonds. Examples of the structure forming the covalent bonds include alkyl, ether, glycol, ester, etc. In the stage before the crosslinking reaction of the silane-modified polyolefin, the modification amount of the silanol unit relative to the main chain ethylene unit is 2% or less.
[0201] The preferred density of the silane grafted modified polyolefin is 0.90 to 0.96 g / cm 3 And the melt mass flow rate (MFR) at 190° C. is 0.2 to 5 g / min.
[0202] The amount of silane-modified polyolefin is preferably 0.5% by mass or more or 3% by mass or more, more preferably 4% by mass or more, and further preferably 5% by mass or more or 6% by mass or more, based on the total amount of the microporous membrane or the A layer from the perspective of good performance of the effect brought by the present invention. The amount of silane-modified polyolefin is preferably 40% by mass or less, more preferably 38% by mass or less, based on the total amount of the microporous membrane from the perspective of cyclicity and safety of the storage device. In addition, the amount of silane-modified polyolefin can be set to 30% by mass or more or 50% by mass or more, and can further be set to 100% by mass, based on the total amount of the A layer.
[0203] The cross-linked structure in the microporous membrane or the layer A is preferably formed by acid, alkali or swelling.
[0204] That is, it is preferred that the cross-linked structure of oligosiloxane bonds formed by immersing the treated object containing silane-modified polyolefin in an alkali (alkali solution) or an acid (acid solution) to perform a silane dehydration condensation reaction is a cross-linked structure in the microporous membrane or layer A. The cross-linked structure in this case is a cross-linked structure obtained by actively promoting the cross-linking reaction in the manufacturing process of the microporous membrane, layer A or separator.
[0205] (Polyethylene)
[0206] In the present specification, polyethylene that may be further contained on the basis of silane-modified polyolefin (polyethylene further contained in the microporous membrane or A layer in the form of a polyolefin different from the silane-modified polyolefin) refers to polyethylene that is a homopolymer having a weight average molecular weight of 100,000 to 10,000,000 or a copolymer containing an alkane unit.
[0207] When the microporous film or the A layer further comprises polyethylene as a polyolefin different from the silane-modified polyolefin, the content thereof is preferably 20% by mass or more, more preferably 40% by mass or more, and further preferably 50% by mass or more, based on the total amount of the silane-modified polyolefin and the polyethylene. If the content of the polyethylene is 20% by mass or more, it is easy to ensure the degradation resistance against oxidation and reduction, and it is also possible to ensure a dense and uniform porous structure.
[0208] On the other hand, the polyethylene content is preferably 97% by mass or less, more preferably 96% by mass or less, and further preferably 95% by mass or less. If the polyethylene content is 97% by mass or less, the content of silane-modified polyolefin in the microporous membrane or layer A can be ensured.
[0209] (Detection method of silane-modified polyolefin contained in separator)
[0210] In the state that the silane-modified polyolefin contained in the separator is cross-linked, it is insoluble or insufficiently soluble in an organic solvent, so it is sometimes difficult to directly measure the content of the silane-modified polyolefin by the separator. In this case, as a pre-treatment of the sample, methyl orthoformate, which does not cause side reactions, is used to decompose the siloxane bond into methoxysilanol, and then a solution NMR measurement is performed, thereby detecting the silane-modified polyolefin contained in the separator. The pre-treatment experiment can be carried out with reference to Japanese Patent Gazette No. 3529854 and Japanese Patent Gazette No. 3529858.
[0211] Specifically, the method for detecting the silane-modified polyolefin contained in the separator can effectively utilize the silane-modified polyolefin as a raw material used in the manufacture of the separator. 1 H or 13 C NMR identification. 1 H and 13 An example of the measurement method of C NMR is described below.
[0212] ( 1 H NMR determination)
[0213] The sample was dissolved in o-dichlorobenzene-d4 at 140° C., and a 1H-NMR spectrum with a proton resonance frequency of 600 MHz was obtained. 1 The measurement conditions of H-NMR are as follows.
[0214] Equipment: AVANCE NEO 600 manufactured by Bruker
[0215] Sample tube diameter: 5mmφ
[0216] Solvent: o-dichlorobenzene-d4
[0217] Measuring temperature: 130℃
[0218] Pulse angle: 30°
[0219] Pulse waiting time: 1sec
[0220] Cumulative times: more than 1000 times
[0221] Sample concentration: 1wt / vol%
[0222] ( 13 C NMR determination)
[0223] The sample was dissolved in o-dichlorobenzene-d4 at 140°C to obtain 13 C-NMR spectroscopy. 13 The measurement conditions of C-NMR are as follows.
[0224] Equipment: AVANCE NEO 600 manufactured by Bruker
[0225] Sample tube diameter: 5mmφ
[0226] Solvent: o-dichlorobenzene-d4
[0227] Measuring temperature: 130℃
[0228] Pulse angle: 30°
[0229] Pulse waiting time: 5sec
[0230] Cumulative times: more than 10,000 times
[0231] Sample concentration: 10wt / vol%
[0232] Figure 4 and Figure 5 It is a product using silane-modified polyolefin raw materials 1 and 2 of two polyolefins. 1 H and 13 C-NMR spectra, and raw materials 1 and 2 have different melt indexes (MI), C3 grafting amounts, C4 grafting amounts and / or silanol modification amounts.
[0233] Figure 4 of 1 H and 13 C-NMR measurement conditions are as follows.
[0234] ( 1 H-NMR measurement conditions)
[0235] Device: Bruker Avance NEO 600
[0236] Observation core: 1 H
[0237] Observation frequency: 600MHz
[0238] Pulse program: zg30
[0239] Pulse waiting time: 1sec
[0240] Cumulative times: 1024 times
[0241] Measuring temperature: 130℃
[0242] Chemical shift standard: 7.219ppm (o-DCBz)
[0243] Solvent: o-dichlorobenzene-d4
[0244] Sample concentration: 1wt / vol%
[0245] Sample tube: 5mmφ
[0246] ( 13 C-NMR measurement conditions)
[0247] Device: Bruker Avance NEO 600
[0248] Observation core: 13 C
[0249] Observation frequency: 150.91MHz
[0250] Pulse program: zgpg30
[0251] Pulse waiting time: 5sec
[0252] Cumulative times: 24000 or 12800
[0253] Measuring temperature: 130℃
[0254] Chemical shift standard: 132.39ppm (o-DCBz)
[0255] Solvent: o-dichlorobenzene-d4
[0256] Sample concentration: 10wt / vol%
[0257] Sample tube: 5mmφ
[0258] Figure 5 of 1 H and 13 C-NMR measurement conditions are as follows.
[0259] ( 1 H-NMR measurement conditions)
[0260] Device: Bruker Avance NEO 600
[0261] Observation core: 1 H
[0262] Observation frequency: 600MHz
[0263] Pulse program: zg30
[0264] Pulse waiting time: 1sec
[0265] Cumulative times: 1024 times
[0266] Measuring temperature: 130℃
[0267] Chemical shift standard: 7.219ppm (o-DCBz)
[0268] Solvent: o-dichlorobenzene-d4
[0269] Sample concentration: 1wt / vol%
[0270] Sample tube: 5mmφ
[0271] ( 13 C-NMR measurement conditions)
[0272] Device: Bruker Avance NEO 600
[0273] Observation core: 13 C
[0274] Observation frequency: 150.91MHz
[0275] Pulse program: zgpg30
[0276] Pulse waiting time: 5sec
[0277] Cumulative times: 12800 times
[0278] Measuring temperature: 130℃
[0279] Chemical shift standard: 132.39ppm (o-DCBz)
[0280] Solvent: o-dichlorobenzene-d4
[0281] Sample concentration: 10wt / vol%
[0282] Sample tube: 5mmφ
[0283] Figure 6 is used Figure 4 The separator made of the silane-modified polyolefin raw material 1 before crosslinking is shown in FIG. 1 H and 13 C-NMR spectrum. Figure 6 of 1 H and 13 C-NMR measurement conditions are as follows.
[0284] ( 1 H-NMR measurement conditions)
[0285] Device: Bruker Avance NEO 600
[0286] Observation core: 1 H
[0287] Observation frequency: 600MHz
[0288] Pulse program: zg30
[0289] Pulse waiting time: 1sec
[0290] Cumulative times: 1024 times
[0291] Measuring temperature: 130℃
[0292] Chemical shift standard: 7.219ppm (o-DCBz)
[0293] Solvent: o-dichlorobenzene-d4
[0294] Sample concentration: 1wt / vol%
[0295] Sample tube: 5mmφ
[0296] ( 13 C-NMR measurement conditions)
[0297] Device: Bruker Avance NEO 600
[0298] Observation core: 13 C
[0299] Observation frequency: 150.91MHz
[0300] Pulse program: zgpg30
[0301] Pulse waiting time: 5sec
[0302] Cumulative times: 24000 or 12800
[0303] Measuring temperature: 130℃
[0304] Chemical shift standard: 132.39ppm (o-DCBz)
[0305] Solvent: o-dichlorobenzene-d4
[0306] Sample concentration: 10wt / vol%
[0307] Sample tube: 5mmφ
[0308] In addition, for the separator in a cross-linked state, after the pre-treatment described above, it can be Figure 6 The same NMR measurement was performed (not shown).
[0309] like Figures 4 to 6 As shown, through 1 H and / or 13 C NMR measurement can confirm the amount of silane units in the silane-modified polyolefin in the polyolefin raw material, the amount of alkyl modification of the polyolefin, etc., and can identify the content of (-CH 2 -Si: 1 H, 0.69ppm, t; 13C, 6.11ppm,s).
[0310] [Combination of microporous membrane and inorganic porous layer]
[0311] The combination of a microporous membrane containing a silane-modified polyolefin and an inorganic porous layer has a tendency to take into account the shutdown function at a lower temperature than 150°C and the film-breaking property at a higher temperature, and to improve the cycle characteristics of the storage device and the battery nail puncture safety. It is speculated that since the silane-modified polyolefin in the microporous membrane is silane cross-linked, if silane cross-linking occurs, the viscosity of the resin in the microporous membrane is sometimes increased. Therefore, when the storage device including the separator is abnormally high in temperature, if a compressive force is applied between multiple electrodes, the cross-linked high-viscosity resin is difficult to flow into the inorganic layer (i.e., difficult to integrate), and the gap between the electrodes can be fully ensured, which can suppress the battery short circuit.
[0312] [Inorganic porous layer]
[0313] The inorganic porous layer is a layer containing inorganic particles and a resin binder, and may further contain a dispersant for dispersing the inorganic particles in the binder resin, if desired.
[0314] The thickness of the inorganic porous layer is preferably 0.5 to 10 μm, 0.5 to 7 μm, 0.5 to 5 μm, or 0.5 to 4 μm from the viewpoint of ion permeability of the separator and charge / discharge capacity or cycle stability of the power storage device. The thickness of the inorganic porous layer can be determined by the method described in Examples.
[0315] [Second porous layer (layer B)]
[0316] The B layer contains inorganic particles. The B layer may further contain a resin binder. In the case where the B layer contains inorganic particles and a resin binder, the B layer may be the inorganic porous layer described above. It should be noted that the B layer may contain components other than the inorganic particles and the resin binder.
[0317] (Thickness of layer B)
[0318] The thickness (TB) of the B layer is preferably 0.2 μm or more, more preferably 0.5 μm or more. If the thickness (TB) is 0.5 μm or more, there is a tendency for the mechanical strength to be further improved. On the other hand, the thickness (TB) is preferably less than 22 μm, more preferably less than 20 μm, and further preferably less than 15 μm. If the thickness (TB) is less than 30 μm, the volume occupied by the separator in the power storage device is reduced, so there is a tendency to be advantageous in terms of the high capacity of the power storage device. In addition, it is also preferred from the perspective of preventing the air permeability of the separator from increasing excessively. It should be noted that the thickness (TB) can be set to, for example, 0.50 μm or more, 0.80 μm or more, or 1.00 μm or more, and can also be set to less than 22.00 μm, less than 20.00 μm, or less than 15.00 μm.
[0319] The thickness (TB) can be measured by the method described in the Examples section, and can also be controlled by changing the coating amount of the coating liquid (slurry) for forming the B layer.
[0320] When the B layer is a single layer, the thickness of the B layer is regarded as the above-mentioned “thickness (TB)”. When the B layer is a plurality of layers, the total thickness of the plurality of B layers is regarded as the above-mentioned “thickness (TB)”.
[0321] When the B layer is disposed on both one side and the other side of the A layer, the total thickness of the B layer disposed on the one side and the B layer disposed on the other side is regarded as the above-mentioned "thickness (TB)".
[0322] (Inorganic particles)
[0323] Examples of inorganic particles include inorganic oxides (oxide ceramics) such as aluminum oxide (Al2O3), silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, cerium oxide, yttrium oxide, zinc oxide, and iron oxide; inorganic nitrides (nitride ceramics) such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum hydroxide (AlO(OH)), potassium titanate, talc, kaolinite, dickite, pearl clay, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and quartz sand; and glass fibers. These may be used alone or in combination of two or more.
[0324] The amount of inorganic particles is based on the total amount of the inorganic porous layer or the B layer, and from the perspective of ensuring heat resistance, it is preferably 5% by mass or more or 20% by mass or more, and more preferably 30% by mass or more. The amount of inorganic particles is based on the total amount of the inorganic porous layer or the B layer, and can be set to 50% by mass or more, more than 80% by mass or more than 85% by mass. On the other hand, the amount of inorganic particles is preferably 99.9% by mass or less, and more preferably 99.5% by mass or less or 99% by mass or less.
[0325] The amount of the inorganic particles may be, for example, 20.00 mass % or more, 30.00 mass % or more, 50.00 mass % or more, more than 80.00 mass % or 85.00 mass % or more, and may be 99.90 mass % or less or 99.50 mass % or less.
[0326] Examples of the shape of the inorganic particles include flakes, scales, needles, columns, spheres, polyhedrons, spindles, and blocks. Inorganic particles having these shapes may be used in combination.
[0327] The number average particle size of the inorganic particles is, for example, 0.01 μm or more, 0.1 μm or more, or 0.3 μm or more, preferably 0.5 μm or more. On the other hand, the number average particle size is, for example, 10.0 μm or less, 9.0 μm or less, or 6.0 μm or less, preferably 2.5 μm or less, more preferably 2.0 μm or less, and further preferably 1.5 μm or less. From the perspective of improving safety during short circuit, the number average particle size of the inorganic particles is preferably adjusted to the above range. As a method for adjusting the number average particle size of the inorganic particles, a method of crushing the inorganic particles using a suitable pulverizing device such as a ball mill, a bead mill, or a jet mill can be cited.
[0328] Regarding the particle size distribution of inorganic particles, the minimum particle size is preferably 0.02 μm or more, more preferably 0.05 μm or more, and further preferably 0.1 μm or more. The maximum particle size is preferably 20 μm or less, more preferably 10 μm or less, and further preferably 7 μm or less. In addition, the ratio of the maximum particle size / average particle size is preferably 50 or less, more preferably 30 or less, and further preferably 20 or less. From the perspective of suppressing thermal shrinkage at high temperatures, it is preferred that the particle size distribution of the inorganic particles is adjusted to the above range. In addition, there may be multiple particle size peaks between the maximum particle size and the minimum particle size. It should be noted that as a method for adjusting the particle size distribution of inorganic particles, for example, a method of crushing an inorganic filler using a ball mill, a bead mill, a jet mill, etc., and adjusting it to a desired particle size distribution, a method of mixing a plurality of fillers having a plurality of particle size distributions after preparing them, etc.
[0329] (resin binder)
[0330] The resin binder includes a resin that binds the inorganic particles together. The glass transition temperature (Tg) of the resin binder is preferably -50°C to 100°C, and more preferably -35°C to 95°C, from the perspective of ensuring adhesion to the inorganic particles and stability of the inorganic porous layer or layer B in the manufacturing process of the separator or the manufacturing process of the storage device or the charging and discharging process.
[0331] The glass transition temperature is determined according to the DSC curve obtained in differential scanning calorimetry (DSC). Specifically, the temperature of the intersection of the straight line obtained by extending the baseline on the low temperature side in the DSC curve to the high temperature side and the tangent line at the inflection point of the step-like change part of the glass transition can be used as the glass transition temperature. In more detail, it can be determined according to the method described in the embodiment. In addition, "glass transition" refers to the heat change that occurs on the endothermic side in DSC accompanied by the state change of the polymer as the test piece. This heat change is observed as a step-like change in the DSC curve. "Step-like change" means the part from the baseline on the previous low temperature side to the baseline on the new high temperature side in the DSC curve. It should be noted that the combination of step-like change and peak is also included in the step-like change. Furthermore, "inflection point" means the point at which the slope of the DSC curve of the step-like change part reaches the maximum. In addition, at the step-like change part, when the upper side is set as the exothermic side, it can also be expressed as a point where the convex curve changes to a convex curve. The "peak" indicates the portion of the DSC curve from when the curve leaves the baseline on the low temperature side to when it returns to the baseline. The "baseline" indicates the DSC curve in the temperature region where the test piece does not undergo transformation or reaction.
[0332] Examples of the resin binder include the following 1) to 7). These may be used alone or in combination of two or more.
[0333] 1) Polyolefins: such as polyethylene, polypropylene, ethylene-propylene rubber and their modified bodies;
[0334] 2) Conjugated diene polymers: for example, styrene-butadiene copolymers and their hydrides, acrylonitrile-butadiene copolymers and their hydrides, acrylonitrile-butadiene-styrene copolymers and their hydrides;
[0335] 3) Acrylic polymers: such as methacrylate-acrylate copolymers, styrene-acrylate copolymers and acrylonitrile-acrylate copolymers;
[0336] 4) Polyvinyl alcohol resins: such as polyvinyl alcohol and polyvinyl acetate;
[0337] 5) Fluorine-containing resins: such as PVdF, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer and ethylene-tetrafluoroethylene copolymer;
[0338] 6) Cellulose derivatives: such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose; and
[0339] 7) Resins having a melting point and / or glass transition temperature of 180°C or higher or polymers having no melting point but a decomposition temperature of 200°C or higher: for example, polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide and polyester.
[0340] These types of resin binders can be obtained by using desired monomers as raw materials according to known production methods such as emulsion polymerization or solution polymerization. In the polymerization, the polymerization temperature, the pressure during polymerization, the method of adding monomers, and the additives used (polymerization initiator, molecular weight modifier, pH modifier, etc.) are not limited.
[0341] The amount of the resin binder is based on the total amount of the inorganic porous layer or the B layer, for example, 0.5 mass % or more or 1.0 mass % or more, and on the other hand, for example, 50 mass % or less or 30 mass % or less. In addition, as described above, with respect to the B layer, the resin binder is an optional component, so the amount of the resin binder contained in the B layer can be set to less than 20 mass %, less than 15 mass % or 0 mass % based on the total amount of the B layer. If the amount of the resin binder contained in the B layer is reduced, the room for the inorganic particles contained in the B layer can be increased accordingly.
[0342] (Dispersant)
[0343] Dispersant is a substance adsorbed on the surface of inorganic particles in the slurry for forming the inorganic porous layer or the B layer, and stabilizes the inorganic particles by electrostatic rebound, etc., and can be, for example, polycarboxylates, sulfonates, polyoxyethers, surfactants, etc. In the inorganic porous layer or the B layer, in addition to the above-mentioned components, other components added and mixed in water-based coatings, etc. can usually be further contained within the scope of its effect. As such other components, there is no particular limitation, and for example, thickeners, film-forming aids, plasticizers, crosslinking agents, antifreeze agents, defoamers, dyes, preservatives, ultraviolet absorbers, light stabilizers, etc. can be listed. These other components can be used alone or in combination of two or more.
[0344] (additive)
[0345] The microporous membrane, the inorganic porous layer, the A layer and / or the B layer may contain known additives as required. Examples of the additives include: organic metal catalysts (dehydration condensation catalysts); plasticizers; antioxidants such as phenolic, phosphorus and sulfur-based antioxidants; metal soaps such as calcium stearate and zinc stearate; thickeners; film-forming aids; crosslinking agents; antifreeze agents; defoamers; preservatives; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; dyes; and coloring pigments.
[0346] Furthermore, the layer B may contain a crosslinking agent. The crosslinking agent may contain a reactive group with the inorganic particles.
[0347] <Physical properties of separator>
[0348] In the case where the separator is used for a higher capacity lithium ion secondary battery, the overall thickness of the separator is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, further preferably 18 μm or less, and particularly preferably 16 μm or less. By making the thickness of the separator 25 μm or less, there is a tendency for the ion permeability to be further improved. The lower limit of the overall thickness of the separator can be, for example, 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, 6.0 μm or more, or 7.5 μm or more.
[0349] The air permeability of the separator is preferably 50 seconds / 100 cm 3 ~400 seconds / 100cm 3 , more preferably 75 seconds / 100cm 3 ~275 seconds / 100cm 3 , more preferably 100 sec / 100 cm 3 ~200 seconds / 100cm 3 If the separator is 50 seconds / 100cm 3 If the air permeability is above 400 sec / 100 cm, it has moderate mechanical strength. 3 The air permeability below 500 nm is preferred because it improves battery characteristics from the viewpoint of permeability.
[0350] <Electrical Storage Device>
[0351] The separator described above can be used in an electrical storage device. The electrical storage device includes a separator of the first embodiment configured between a plurality of electrodes, and an electrolyte. The electrodes are, for example, a positive electrode, a negative electrode, etc., and the separator is preferably configured between the positive and negative electrodes. As electrical storage devices, specifically, there can be listed: lithium batteries, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel-hydrogen batteries, nickel-cadmium batteries, double-layer capacitors, lithium ion capacitors, redox flow batteries, lithium-sulfur batteries, lithium-air batteries, zinc-air batteries, etc. Among these, from the perspective of practicality, lithium batteries, lithium secondary batteries, lithium ion secondary batteries, nickel-hydrogen batteries or lithium ion capacitors are preferred, and lithium batteries or lithium ion secondary batteries are more preferred.
[0352] <Lithium-ion secondary battery>
[0353] A lithium-ion secondary battery is a storage battery that uses a lithium transition metal oxide such as lithium cobalt oxide or lithium cobalt composite oxide as a positive electrode, a carbon material such as graphite or black lead as a negative electrode, and an organic solvent containing a lithium salt such as LiPF6 as an electrolyte. The electrolyte described above in connection with the manufacturing method of the separator may also be used for a lithium-ion secondary battery. During the charge / discharge of the lithium-ion secondary battery, the ionized lithium moves back and forth between the electrodes. In addition, it is necessary to suppress the contact between the electrodes while allowing the aforementioned ionized lithium to move between the electrodes at a relatively high speed, so a separator is arranged between the electrodes.
[0354] <Method for manufacturing separator for power storage device>
[0355] Another embodiment of the present invention is a method for manufacturing a separator for a power storage device. The method for manufacturing the separator may include, for example, a process for manufacturing a microporous membrane or layer A, and a process for manufacturing an inorganic porous layer on the microporous membrane as desired, or a process for manufacturing layer B on layer A. The material used in the method for manufacturing the separator may be the material described in the first or second embodiment unless otherwise specified.
[0356] <Third Embodiment>
[0357] The method for producing a microporous membrane according to the third embodiment includes the following steps:
[0358] (1) Sheet forming process;
[0359] (2) Stretching process;
[0360] (3) porous body forming step;
[0361] (4) Heat treatment process;
[0362] (5) Affinity treatment process;
[0363] (6) a cross-linking treatment step; and
[0364] (7) Washing and drying process.
[0365] The above-described layer A can also be formed by performing steps (1) to (7). The method for producing a microporous membrane of the third embodiment may include a kneading step before the sheet forming step (1) and / or a winding step after the water washing and drying step (7) as desired.
[0366] The method for manufacturing the separator may further include the following steps in addition to steps (1) to (7) as desired:
[0367] (8A) A step of coating an inorganic porous layer on a silane-crosslinked microporous membrane. The inorganic porous layer is coated on the microporous membrane that has been silane-crosslinked in steps (1) to (7) in step (8A), so that there is a tendency for the coating property on the microporous membrane and the wettability of the microporous membrane to be improved in the manufacturing process of the separator.
[0368] [Mixing process]
[0369] The kneading step is a step of kneading the silane-grafted modified polyolefin with other polyolefins to obtain a kneaded product. In the kneading step, polyethylene and the silane-grafted modified polyolefin are preferably used in combination. The silane-grafted modified polyolefin, the silane-unmodified polyethylene, and the polyolefins other than these may be the substances described in relation to the first embodiment. In the kneading step, the silane-grafted modified polyolefin may be kneaded with a plasticizer as desired.
[0370] In addition, the kneading process preferably uses a polyolefin composition containing a polyolefin having a weight average molecular weight of less than 1,000,000 (relative to the whole polyolefin, preferably 40% by mass or more, more preferably 80% by mass or more). By using a polyolefin having a weight average molecular weight of less than 1,000,000, there is a tendency to relax the shrinkage of the polymer in the early stage in the heating test of the storage device, especially in the heating safety test, which is easy to maintain safety. It should be noted that if the case of using a polyolefin having a weight average molecular weight of less than 1,000,000 is compared with the case of using a polyolefin having a weight average molecular weight of more than 1,000,000, there is a tendency for the elastic modulus of the obtained microporous film in the thickness direction to decrease, so that a microporous film with a concave and convex shape that is easier to transfer to the core can be obtained.
[0371] The polyolefin composition used in the kneading step may contain known additives such as a dehydration condensation catalyst, a plasticizer, metal soaps such as calcium stearate and zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a coloring pigment.
[0372] (Dehydration condensation catalyst)
[0373] Alkoxysilyl forms siloxane bonds through a hydrolysis reaction based on water. However, due to its slow reaction rate, an organic metal catalyst is used in most cases to promote the condensation reaction. The metal containing the organic metal catalyst can be, for example, at least one selected from the group consisting of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel and lead. Regarding organic metal catalysts, it is known that these substances listed as dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctoate, etc., are based on the reaction mechanism proposed by Weij et al. (FW van. der. Weij: Macromol. Chem., 181, 2541, 1980.) and can overwhelmingly promote the reaction rate, but in recent years, in order to avoid the health hazards to the environment and human body caused by organic tin, it is known that by utilizing the Lewis function of the chelate complex of copper or titanium and combining with an organic base, the reaction of forming siloxane bonds between alkoxysilyl groups can be promoted in the same manner as the organic tin complex.
[0374] (Masterbatch resin)
[0375] It is known that the dehydration condensation catalyst also functions as a catalyst for the siloxane bond formation reaction of the alkoxysilyl-containing resin. In this specification, a substance obtained by adding a dehydration condensation catalyst (or an organic metal catalyst) to an alkoxysilyl-containing resin or other mixed resin in advance and mixing in a continuous process having a resin mixing step using an extruder is referred to as a masterbatch resin.
[0376] (Plasticizer)
[0377] The plasticizer is not particularly limited, and examples thereof include organic compounds that can form a uniform solution with polyolefin at a temperature below the boiling point. More specifically, decalin, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decanol, nonanol, diphenyl ether, n-decane, n-dodecane, paraffin oil, etc. Among these, paraffin oil and dioctyl phthalate are preferred. The plasticizer may be used alone or in combination of two or more.
[0378] The ratio of the plasticizer is preferably 20% by mass or more based on the total mass of the polyolefin from the viewpoint of the porosity of the obtained microporous membrane, and is preferably 90% by mass or less from the viewpoint of the viscosity during melt kneading.
[0379] [Sheet forming process (extrusion process)]
[0380] The sheet forming step is a step of extruding the obtained kneaded product, or the mixture of silane grafted modified polyolefin, polyethylene and plasticizer, cooling and solidifying, and molding into a sheet to obtain a sheet. The sheet forming method is not particularly limited, and examples thereof include a method of solidifying the melt kneaded and extruded melt by compression cooling. Examples of cooling methods include: (i) a method of direct contact with a cooling medium such as cold air or cooling water; (ii) a method of contacting a roller or press cooled with a refrigerant, etc., and method (ii) is preferred in terms of excellent film thickness controllability.
[0381] From the perspective of resin agglomerates or the maximum internal heat release rate in the separator, in the sheet forming process, the weight ratio of silane grafted modified polyolefin to polyethylene (silane grafted modified polyolefin weight / polyethylene weight) is preferably 0.05 / 0.95 to 0.40 / 0.60, and more preferably 0.06 / 0.94 to 0.38 / 0.62.
[0382] [Stretching process]
[0383] The stretching process is a process of extracting plasticizers and inorganic materials from the obtained sheet as needed and further stretching the sheet in one or more directions. As the stretching method of the sheet, there can be listed: MD uniaxial stretching based on a roll stretcher, TD uniaxial stretching based on a stenter, sequential biaxial stretching based on a combination of a roll stretcher and a stenter or a stenter and a stenter, and biaxial stretching based on a simultaneous biaxial stenter and inflation molding. From the perspective of obtaining a more uniform film, simultaneous biaxial stretching is preferred.
[0384] The total surface ratio is preferably more than 8 times, more preferably more than 15 times, further preferably more than 20 times or more than 30 times from the perspective of the balance of uniformity, tensile elongation and porosity of film thickness and average pore size. By making the total surface ratio more than 8 times, there is a tendency to easily obtain a sheet with high strength and good thickness distribution. In addition, this surface ratio can be less than 250 times from the perspective of preventing fracture, etc.
[0385] [Porous body forming step (extraction step)]
[0386] The porous body forming step is a step of extracting the plasticizer from the stretched product after the stretching step and making the stretched product porous.
[0387] There are no particular limitations on the method for extracting the plasticizer, and examples thereof include: a method of immersing the stretched article in an extraction solvent, a method of spraying the stretched article with the extraction solvent, and the like. There are no particular limitations on the extraction solvent, and for example, a solvent that is a poor solvent for polyolefins and a good solvent for plasticizers and inorganic materials, and has a boiling point lower than the melting point of polyolefins is preferred. There are no particular limitations on such an extraction solvent, and examples thereof include: hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane, 1,1,1-trichloroethane, and fluorocarbons; alcohols such as ethanol and isopropanol; ketones such as acetone and 2-butanone; alkaline water, and the like. One extraction solvent may be used alone, or two or more may be used in combination.
[0388] [Heat treatment process]
[0389] The heat treatment step is a step of further extracting a plasticizer from the sheet as necessary after the stretching step and further performing heat treatment to obtain a microporous membrane.
[0390] The method of heat treatment is not particularly limited, and for example, a heat setting method using a stenter or a roller stretching machine for stretching and relaxation operations can be cited. The relaxation operation refers to a shrinking operation performed at a specified temperature and relaxation rate along the machine direction (MD) and / or width direction (TD) of the film. The relaxation rate refers to a value obtained by dividing the MD size of the film after the relaxation operation by the MD size of the film before the operation, or a value obtained by dividing the TD size of the film after the relaxation operation by the TD size of the film before the operation, or when both MD and TD are relaxed, it refers to a value obtained by multiplying the relaxation rate of MD by the relaxation rate of TD.
[0391] In the present embodiment, from the viewpoint of obtaining a heat-treated porous body suitable for the affinity treatment step and the cross-linking treatment step, it is preferred to perform stretching and relaxation along the TD of the porous body.
[0392] [Affinity treatment process]
[0393] The affinity treatment step is a step of immersing the microporous membrane obtained in the heat treatment step in an organic solvent having amphiphilicity to water and organic matter in order to improve the wettability between water and polyolefin. In this embodiment, an amphiphilic organic solvent is arranged inside the porous body after affinity treatment, so that the affinity with liquid is increased, for example, the affinity with the material or catalyst that promotes the crosslinking reaction in the crosslinking treatment step is sometimes increased.
[0394] The organic solvent used is not particularly limited, and examples thereof include alcohols, acetone, ethylene carbonate, N-methyl-2-pyrrolidone, dimethyl sulfoxide, etc. In addition, the immersion method includes immersing the heat-treated porous body in an organic solvent, spraying the heat-treated porous body with an organic solvent, etc.
[0395] [Cross-linking treatment process]
[0396] The cross-linking treatment step is a step of reacting the alkoxysilyl groups contained in the microporous membrane obtained in the affinity treatment step to form siloxane bonds (cross-linking reaction).
[0397] In this embodiment, the affinity-treated porous body is brought into contact with a mixture containing an organic metal catalyst and water, or is immersed in an alkaline solution or an acid solution to cause a silane dehydration condensation reaction to form an oligomeric siloxane bond.
[0398] Conventional formed products such as hot water pipes have Sn-based catalysts put into the extruder during the extrusion process, but in the manufacturing process of the separator for the power storage device, if silane crosslinking is promoted in the extruder during the sheet forming process, the gelled part will lead to poor production, and it will be difficult to stretch the silane crosslinked polyolefin in the stretching process as a subsequent process. Therefore, in this embodiment, the silane crosslinking treatment is performed after the stretching process, the heat treatment process, and the affinity treatment process, and the heat resistance, shape retention, and film breakage resistance of the separator are ensured by the silane crosslinking part.
[0399] The metal containing the organometallic catalyst may be, for example, at least one selected from the group consisting of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel and lead, among which tin, zinc or palladium is preferred, and tin or zinc is more preferred. The organotin complex that can be used as a catalyst may be, for example, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctoate, stannous acetate, stannous octoate, etc.
[0400] The pH of the alkaline solution exceeds 7, and may contain, for example, alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkali metal phosphates, ammonia, amine compounds, etc. Among these, alkali metal hydroxides or alkaline earth metal hydroxides are preferred, alkali metal hydroxides are more preferred, and sodium hydroxide is further preferred from the viewpoint of the safety of the power storage device and the silane crosslinking property.
[0401] The pH of the acid solution is less than 7, and may contain, for example, an inorganic acid, an organic acid, etc. Preferred acids are hydrochloric acid, sulfuric acid, carboxylic acids, or phosphoric acids.
[0402] The cross-linking treatment step is preferably performed by immersing the affinity-treated porous body in an alkaline solution or an acid solution from the viewpoint of suppressing a thermal runaway reaction when the power storage device is destroyed and improving safety.
[0403] When the affinity-treated porous body is immersed in an alkaline solution, from the perspective of further improving safety, the temperature of the alkaline solution is preferably 20° C. to 100° C., and / or the pH of the alkaline solution is preferably 8 to 14. The reagent used for pH adjustment is not particularly limited, and examples thereof include alkali metal hydroxides, alkaline earth metal hydroxides, etc. From the same perspective, the alkaline aqueous solution preferably does not contain amine compounds such as ethylamine, dibutylamine, hexylamine, and pyridine.
[0404] When the affinity-treated porous body is immersed in an acid solution, although not wishing to be bound by theory, it is presumed that the acid catalyzes the formation of Si-O bonds of the silane-crosslinked polyolefin rather than cleaving the Si-O bonds of the silane-crosslinked polyolefin.
[0405] In the case of contacting the affinity-treated porous body with a mixture containing an organic metal catalyst and water, from the perspective of controlling the amorphous part of the microporous membrane and ensuring safety, the content of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel or lead in the final microporous membrane is preferably adjusted to a range of 0.10 ppm or more and 200 ppm or less in terms of the total amount converted by atoms, and the content of zinc or tin in the microporous membrane is more preferably adjusted to a range of 0.10 ppm or more and 200 ppm or less in terms of the total amount converted by atoms. The content of scandium, vanadium, copper, zinc, zirconium, palladium, gallium, tin, titanium, iron, nickel or lead in the microporous membrane can be adjusted, for example, by the water washing and drying process described later. It was found that by such a limited range of metal content, while suppressing the decomposition of the cross-linked structure of the porous membrane and ensuring safety, the battery cycle characteristics showed good performance. The present inventors have found that when an excessive amount of metal is contained in a separator for an electricity storage device, eluted ions penetrate into the positive electrode, changing the structure of the metal cluster storing Li, causing electrical defect points to form throughout the positive electrode, and deteriorating the cycle performance.
[0406] [Washing and drying process]
[0407] The water washing and drying step is a step of washing and drying the microporous membrane obtained in the above cross-linking treatment step. The preferred conditions of the water washing and drying step are that the water temperature is 20 to 100° C. and / or the pH of the washing water is 6 to 8. For example, the microporous membrane can be dried after replacing the water with pH 6 to 8 at a temperature of 20 to 100° C. The drying method is not particularly limited, and examples thereof include conveying with a heating roller, blowing hot air, or heating and drying with an infrared heater.
[0408] [Inorganic porous layer coating step]
[0409] The inorganic porous layer coating step (8A) is a step of forming an inorganic porous layer containing inorganic particles and a resin binder on at least one surface of the microporous membrane obtained above. The inorganic porous layer coating step (8A) can be performed after the silane crosslinking reaction of the silane graft-modified polyolefin.
[0410] The B layer described above can also be formed by performing a coating step (8A). As a method for forming the B layer, a known manufacturing method can be used. As a method for making a laminate including an A layer and a B layer, for example, there can be cited: a method of applying a slurry containing inorganic particles to the A layer, a method of laminating and extruding the raw material of the B layer and the raw material of the A layer by a co-extrusion method, a method of laminating the A layer and the B layer after separately making them, etc.
[0411] The inorganic porous layer can be formed, for example, by coating a slurry comprising inorganic particles, a resin binder, water or an aqueous solvent (e.g., a mixture of water and an alcohol, etc.) and a dispersant as desired on the surface of at least one side of the microporous membrane. The inorganic particles, the resin binder and the dispersant can be as described in the description of the first or second embodiment.
[0412] The solvent contained in the slurry is preferably a solvent that can uniformly and stably disperse or dissolve the inorganic particles. Examples of the solvent include N-methylpyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, toluene, hot xylene, dichloromethane, and hexane.
[0413] Examples of the method for preparing the slurry containing inorganic particles include mechanical stirring methods using a ball mill, a bead mill, a planetary ball mill, a vibration ball mill, a sand mill, a colloid mill, an attritor, a roll mill, a high-speed impeller dispersion, a disperser, a homogenizer, a high-speed impact mill, ultrasonic dispersion, and a stirring blade.
[0414] Examples of the coating method for the slurry containing inorganic particles include a gravure coater method, a small-diameter gravure coater method, a reverse roll coater method, a transfer roll coater method, a kiss coater method, a dip coater method, a knife coater method, an air knife coater method, a blade coater method, a rod coater method, an extrusion coater method, a cast coater method, a die coater method, a screen printing method, and a spray coating method.
[0415] Methods for removing the solvent from the coating film include drying at a temperature below the melting point of the material constituting the microporous film, drying under reduced pressure at low temperature, etc. In addition, a portion of the solvent may remain as long as it does not significantly affect the device characteristics.
[0416] [Winding / slitting process]
[0417] The winding step is a step of slitting the obtained microporous membrane or the microporous membrane coated with the inorganic porous layer as required and winding the resulting microporous membrane around a predetermined core.
[0418] The separator obtained by the method including the various steps described above can be used in a power storage device, particularly a lithium battery or a lithium ion secondary battery.
[0419] <Method for manufacturing power storage device>
[0420] The method for manufacturing an electric storage device comprises the following steps;
[0421] (I) a step of stacking and / or winding a positive electrode, a separator produced by the method of the third embodiment, and a negative electrode to obtain a stacked body or a wound body;
[0422] (II) a step of placing the laminate or wound body into an outer shell;
[0423] (III) a step of injecting an electrolyte into the outer shell; and
[0424] (IV) A step of connecting lead terminals to the positive electrode and the negative electrode.
[0425] In addition to using the separator for the storage device manufactured by the method of the third embodiment, steps (I) to (IV) can be carried out by a method known in the technical field. In addition, in steps (I) to (IV), a positive electrode, a negative electrode, an electrolyte solution and an outer shell known in the technical field can be used.
[0426] Based on step (I), a longitudinal separator with a width of 10 to 500 mm (preferably 80 to 500 mm) and a length of 200 to 4000 m (preferably 1000 to 4000 m) can be manufactured. Next, in step (I), the positive electrode-separator-negative electrode-separator or negative electrode-separator-positive electrode-separator can be stacked in the order of positive electrode-separator-negative electrode-separator, and wound into a circular or flat spiral to obtain a wound body. In steps (II) and (III), the wound body can be placed in a device can (such as a battery can) and further injected with a non-aqueous electrolyte to manufacture a power storage device. In addition, the power storage device can also be manufactured by placing the wound body made by folding the electrodes and separators into a device container (such as an aluminum film) and injecting a non-aqueous electrolyte.
[0427] At this time, the wound body may be pressed. Specifically, a separator and an electrode including a current collector and an active material layer formed on at least one surface of the current collector may be stacked and pressed.
[0428] Regarding the pressing temperature, as a temperature at which adhesion can be effectively exhibited, for example, it is preferably 20°C or more. In addition, from the perspective of suppressing the clogging or thermal shrinkage of the pores in the separator caused by hot pressing, the pressing temperature is preferably lower than the melting point of the material contained in the microporous membrane, and more preferably 120°C or less. From the perspective of suppressing the clogging of the pores in the separator, the pressing pressure is preferably 20 MPa or less. Regarding the pressing time, when roller pressing is used, it can be less than 1 second, or it can be a surface pressure of several hours. From the perspective of productivity, it is preferably less than 2 hours.
[0429] By going through the above manufacturing process, it is possible to suppress the back push (press back) when the wound body composed of electrodes and separators is press-formed. Therefore, it is possible to suppress the reduction of the yield rate in the device assembly process and shorten the production process time, which is preferable.
[0430] The electrolyte used in step (III) may include fluorine (F)-containing lithium salts such as LiPF6, LiBF4, LiN(SO2CF3)2, LiSO3CF3, or electrolytes such as LiBC4O8 (LiBOB), preferably an electrolyte containing LiPF6 or other F-containing electrolytes, and a non-aqueous solvent.
[0431] Example
[0432] The present invention is described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples unless it exceeds the gist of the present invention. It should be noted that the physical properties in the Examples were measured by the following methods.
[0433] <Weight average molecular weight (Mw)>
[0434] ALC / GPC 150C (trademark) manufactured by Waters was used to measure standard polystyrene under the following conditions to prepare a calibration curve. In addition, chromatograms were measured for each of the following polymers under the same conditions, and the weight average molecular weight of each polymer was calculated based on the calibration curve by the following method.
[0435] Chromatographic columns: 2 GMH6-HT (trademark) + 2 GMH6-HTL (trademark) manufactured by Tosoh Corporation
[0436] Mobile phase: o-dichlorobenzene
[0437] Detector: Differential Refractometer
[0438] Flow rate: 1.0ml / min
[0439] Column temperature: 140°C
[0440] Sample concentration: 0.1wt%
[0441] (Weight average molecular weight of polyethylene)
[0442] The molecular weight distribution curve converted to polyethylene was obtained by multiplying each molecular weight component in the obtained calibration curve by 0.43 (Q factor of polyethylene / Q factor of polystyrene=17.7 / 41.3), and the weight average molecular weight was calculated.
[0443] (Weight average molecular weight of resin composition)
[0444] The weight average molecular weight was calculated in the same manner as in the case of polyethylene, except that the Q factor value of the polyolefin having the largest mass fraction was used.
[0445] <Viscosity Average Molecular Weight (Mv)>
[0446] The intrinsic viscosity [η] at 135° C. in a decalin solvent was determined based on ASTM-D4020. The Mv of polyethylene was calculated according to the following formula.
[0447] [η] = 6.77 × 10 -4 Mv 0.67
[0448] <Melt flow rate (MFR) (g / 10min)>
[0449] The weight of a resin product extruded for 10 minutes at 190° C. and a load of 2.16 kg was determined as an MFR value using a melt flow rate measuring instrument (MELT INDEXER F-F01) manufactured by Toyo Seiki Co., Ltd.
[0450] <Determination of Glass Transition Temperature>
[0451] Take an appropriate amount of a water dispersion containing a resin sample (solid content = 38-42% by weight, pH = 9.0) into an aluminum dish and dry it in a hot air dryer at 130°C for 30 minutes to obtain a dry film. About 17 mg of the dry film is filled into an aluminum container for measurement, and a DSC curve and a DSC curve under a nitrogen atmosphere are obtained using a DSC measuring device (manufactured by Shimadzu Corporation, model "DSC6220"). The measurement conditions are as follows.
[0452] The first heating program: Start from 70℃, increase the temperature at a rate of 15℃ per minute. After reaching 110℃, maintain it for 5 minutes.
[0453] The second cooling program: start from 110℃ and cool at a rate of 40℃ per minute. After reaching -50℃, maintain for 5 minutes.
[0454] The third temperature increase program: the temperature was increased from -50°C to 130°C at a rate of 15°C per minute. DSC and DDSC data were obtained during the third temperature increase.
[0455] The intersection point of the baseline (a straight line obtained by extending the baseline in the DSC curve obtained to the high-temperature side) and the tangent line at the inflection point (the point where the upwardly convex curve changes to the downwardly convex curve) is taken as the glass transition temperature (Tg).
[0456] <Film thickness (μm)>
[0457] The film thickness of the microporous membrane or the separator is measured at room temperature of 23 ± 2 °C and relative humidity of 60% using a micro-thickness gauge, KBM (trademark), manufactured by Toyo Seiki Seisaku-sho, Ltd. Specifically, the film thickness at 5 points is measured at substantially equal intervals along the entire width in the TD direction, and their average value is obtained. The thickness of the inorganic porous layer can be calculated by subtracting the film thickness of the microporous membrane from the thickness of the separator composed of the microporous membrane and the inorganic porous layer.
[0458] <Thickness of layer A (TA) and thickness of layer B (TB)>
[0459] The thickness of layer A (TA) is measured at room temperature of 23 ± 2 °C and relative humidity of 60% using a micro-thickness gauge, KBM (trademark), manufactured by Toyo Seiki Seisaku-sho, Ltd. Specifically, the film thickness at 5 points is measured at substantially equal intervals along the entire width in the TD direction, and their average value is obtained. In addition, by the same method, the thickness of the laminate including layer A and layer B is obtained. Then, the thickness of layer B (TB) is obtained by subtracting the thickness of layer A (TA) from the thickness of the obtained laminate.
[0460] The thickness of the obtained laminate is regarded as the total thickness of layer A and layer B (TA + TB). In addition, by dividing the thickness (TA) by the thickness (TB), the thickness ratio (TA / TB) is obtained.
[0461] <Porosity (%)>
[0462] (i) Calculated based on the density of the mixed composition
[0463] A 10 cm × 10 cm square sample is cut from the microporous membrane, and its volume (cm 3 ) and mass (g) are obtained. Based on these and the density (g / cm 3 ), the porosity is calculated using the following formula. It should be noted that the density of the mixed composition is the value calculated and obtained based on the respective densities and mixing ratios of the raw materials used.
[0464] Porosity (%) = (Volume - Mass / Density of the mixed composition) / Volume × 100
[0465] (ii) Calculated based on the film density
[0466] Alternatively, the porosity of the microporous membrane is calculated from the volume, mass, and film density (g / cm 3 ) using the following formula.
[0467] Porosity (%) = (Volume - Mass / Membrane density) / Volume × 100
[0468] It should be noted that in the present invention, the membrane density refers to the value measured by the D) density gradient tube method described in JIS K7112 (1999).
[0469] (iii) Porosity of layer A
[0470] Cut a 10 cm × 10 cm square sample from layer A, and find its volume (cm 3 ) and mass (g). Based on these and the density (g / cm 3 ), use the following formula to calculate the porosity. The density of the mixed composition is the value calculated and obtained based on the respective densities and mixing ratios of the raw materials used.
[0471] Porosity (%) = (Volume - Mass / Density of the mixed composition) / Volume × 100
[0472] <Air permeability (sec / 100 cm 3 )>
[0473] According to JIS P-8117 (2009), use a GURLEY type air permeability tester, G-B2 (trademark) manufactured by Toyo Seiki Co., Ltd. to measure the air permeability of the sample or layer A.
[0474] <Puncture strength of layer A>
[0475] Use a portable compression tester KES-G5 (model) manufactured by KATO TECH Co., Ltd., and fix layer A with a sample holder having an opening diameter of 11.3 mm. Then, for the central part of the fixed layer A, use a needle with a tip curvature radius of 0.5 mm, and perform a puncture test at a puncture speed of 2 mm / second in an atmosphere of 25°C to measure the maximum puncture load. Convert this maximum puncture load into a value equivalent to a thickness of 20 μm, and use this value as the puncture strength (gf / 20 μm). In the case where the thermoplastic polymer exists only on one side of the substrate, the needle can be punctured from the side where the thermoplastic polymer exists.
[0476] <Quantification of resin condensates in the separator>
[0477] The resin condensates in the separator are defined as regions that are opaque and have an area of 100 μm in length × 100 μm in width or more when observing the separator obtained through the film formation process of the following Examples and Comparative Examples using a transmission type optical microscope. In the observation based on the transmission type optical microscope, measure the number of resin condensates per 1000 m 2 of the separator area.
[0478] <TMA film breaking temperature>
[0479] Using the constant length mode of TMA50 (trademark) manufactured by Shimadzu Corporation, the environmental temperature is varied between 25 and 250 °C, and the temperature at the moment when the load is completely released is determined as the TMA film breaking temperature.
[0480] Specifically, when measuring the MD direction, a microporous membrane with a size of 3 mm in the TD direction and 14 mm in the MD direction is taken. The two ends in the MD direction are clamped by a special probe, the clamp spacing is set to 10 mm, an initial load of 1.0 g is applied, the furnace carrying the test piece is heated, and the temperature at which the load shows 0 g is taken as the TMA film breaking temperature.
[0481] When measuring the TD direction, a microporous membrane with a size of 14 mm in the TD direction and 3 mm in the MD direction is taken. The two ends in the TD direction are clamped by a special probe, the clamp spacing is set to 10 mm, an initial load of 1.0 g is applied, and the same operation as above is carried out.
[0482] <Film breaking temperature of layer A>
[0483] Using the constant length mode of TMA50 (trademark) manufactured by Shimadzu Corporation, the environmental temperature is varied between 25 and 250 °C, and the temperature at the moment when the load is completely released is determined as the TMA film breaking temperature (the film breaking temperature of layer A measured by TMA).
[0484] Specifically, 3 mm in the TD direction and 14 mm in the MD direction are taken from layer A and used as a specimen piece (a specimen piece with the MD as the long side). The two ends of the MD of the specimen piece are installed on a special probe with a clamp spacing of 10 mm, and a load of 1.0 g is applied to the specimen piece. The furnace carrying the test piece is heated, and the temperature at which the load shows 0 g is taken as the film breaking temperature (°C).
[0485] It should be noted that when measuring the TD of a specimen piece with the TD as the long side, 14 mm in the TD direction and 3 mm in the MD direction are taken from layer A and used as a specimen piece. The two ends in the TD direction are clamped by a special probe, the clamp spacing is set to 10 mm, an initial load of 1.0 g is applied, and the same operation as above is carried out.
[0486] <Thermal shrinkage rate at 150 °C>
[0487] A specimen piece with a size of 100 mm in the TD direction and 100 mm in the MD direction is taken from the laminate (the laminate including layer A and layer B) before the crosslinked structure is formed. And the specimen piece is left standing in an oven at 150 °C for 1 hour. At this time, the specimen piece is clamped with two pieces of paper so that the hot air does not directly blow on the specimen piece. After the specimen piece is taken out of the oven and cooled, the area of the specimen piece is measured, and the thermal shrinkage rate (T1) at 150 °C before the crosslinked structure is formed is calculated according to the following formula.
[0488] Thermal shrinkage at 150°C (%) = (10,000 (mm 2 )-area of the heated specimen (mm 2 ))×100 / 10,000
[0489] In addition, about the laminated body after forming the crosslinked structure, TD100mm, MD100mm was taken as a test piece, and the same operation as above was carried out to calculate the heat shrinkage rate (T2) at 150°C after forming the crosslinked structure.
[0490] Then, the ratio (T2 / T1) is obtained by dividing the heat shrinkage rate (T2) by the heat shrinkage rate (T1). The value of this ratio (T2 / T1) is equivalent to the change ratio of the heat shrinkage rate (T2) at 150°C after the cross-linked structure is formed relative to the heat shrinkage rate (T1) at 150°C before the cross-linked structure is formed.
[0491] <Battery destruction safety test 1>
[0492] Battery destruction safety test 1 is a test in which an iron nail is driven into a battery charged to 4.5V at a speed of 20mm / sec and penetrated to cause an internal short circuit. This test can clarify the phenomenon during an internal short circuit by measuring the time change behavior of the battery voltage drop caused by the internal short circuit and the battery surface temperature rise caused by the internal short circuit. In addition, due to the insufficient closing function of the separator during an internal short circuit and the rupture of the membrane at low temperature, the battery sometimes releases heat rapidly, and the electrolyte sometimes catches fire, and the battery smokes and / or explodes.
[0493] (Preparation of Batteries Used in Battery Destruction Safety Test 1)
[0494] 1a. Preparation of positive electrode
[0495] Take 92.2% by mass of lithium cobalt composite oxide LiCoO2 as the positive electrode active material, 2.3% by mass of flaky graphite and acetylene black as the conductive material, and 3.2% by mass of polyvinylidene fluoride (PVDF) as the resin binder, and disperse them in N-methylpyrrolidone (NMP) to prepare a slurry. Use a die coater to apply the slurry on one side of a 20 μm thick aluminum foil constituting the positive electrode collector, dry it at 130°C for 3 minutes, and then use a roller press to perform compression molding. At this time, adjust the coating amount of the positive electrode active material to 250 g / m 2 , the volume density of the active material is adjusted to 3.00 g / cm 3 .
[0496] 1b. Preparation of negative electrode
[0497] 96.9% artificial graphite as negative electrode active material, 1.4% ammonium salt of carboxymethyl cellulose as resin binder and 1.7% styrene-butadiene copolymer latex as resin binder were dispersed in purified water to prepare slurry. The slurry was applied to one side of a copper foil with a thickness of 12 μm constituting the negative electrode current collector using a die coater, dried at 120°C for 3 minutes, and then compression molded using a roller press. At this time, the amount of negative electrode active material applied was adjusted to 106 g / m 2 , the volume density of the active material was adjusted to 1.35 g / cm 3 .
[0498] 1c. Preparation of non-aqueous electrolyte
[0499] A non-aqueous electrolyte was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L.
[0500] 1d.Battery assembly
[0501] The separator is cut into 60 mm in the width (TD) direction and 1000 mm in the length (MD) direction, and the separator is folded repeatedly, and the positive electrode and the negative electrode (12 positive electrodes and 13 negative electrodes) are alternately stacked between the separators. It should be noted that the positive electrode uses an area of 30 mm × 50 mm and the negative electrode uses an area of 32 mm × 52 mm. After the repeatedly folded stack is put into a laminated bag, the non-aqueous electrolyte obtained in the above c. is injected and sealed. After being placed at room temperature for 1 day, the battery voltage is charged to 4.2V at a current value of 3mA (0.5C) in an atmosphere of 25°C. After reaching 4.2V, the current value is reduced from 3mA to maintain 4.2V. This method is used for the initial charge after the battery is made for a total of 6 hours. Then, the battery voltage is discharged to 3.0V at a current value of 3mA (0.5C).
[0502] (Maximum heat release rate)
[0503] After an iron nail was passed through the obtained battery, the battery surface temperature was measured for 300 seconds using a thermocouple to obtain a temperature change graph, and the rate at which the temperature rise per 1 second was the largest was determined as the maximum heat release rate.
[0504] (Voltage drop time)
[0505] After an iron nail was passed through the obtained battery, the time required for the voltage to decrease from 4.5 V to 3 V was determined as the voltage decrease time (time until the voltage decreased to 3 V).
[0506] <Evaluation of cycle characteristics and method for producing a battery>
[0507] A battery for evaluating cycle characteristics was prepared in the same manner as 1a. to 1c. of the method for preparing the battery used in the above item <Battery destruction safety test 1>, except that the assembly was performed according to the following 1d-2.
[0508] 1d-2. Battery assembly
[0509] Cut the separator into a circle with a diameter of 18 mm, cut the positive electrode and the negative electrode into a circle with a diameter of 16 mm, and stack the positive electrode, separator, and negative electrode in order so that the active material surfaces of the positive electrode and the negative electrode face each other, and place them in a stainless steel metal container with a lid. The container is insulated from the lid, the container is in contact with the copper foil of the negative electrode, and the lid is in contact with the aluminum foil of the positive electrode. The non-aqueous electrolyte obtained in 1c. of the above item <Battery Destruction Safety Test 1> is injected into the container and sealed. After being placed at room temperature for 1 day, charge at a current value of 3mA (0.5C) to a battery voltage of 4.2V in an atmosphere of 25°C. After reaching 4.2V, the current value is reduced from 3mA to maintain 4.2V. This method is used for the initial charge after the battery is made for a total of 6 hours. Next, discharge at a current value of 3mA (0.5C) to a battery voltage of 3.0V.
[0510] The battery was charged and discharged for 100 cycles at 60°C. The battery was charged at a current value of 6.0 mA (1.0 C) until the battery voltage reached 4.2 V, and then the current value was reduced from 6.0 mA to maintain 4.2 V. The battery was charged for a total of 3 hours in this manner. The battery was discharged at a current value of 6.0 mA (1.0 C) until the battery voltage reached 3.0 V.
[0511] (Cycle Characteristics Evaluation 1)
[0512] The capacity retention rate was calculated from the discharge capacity at the 100th cycle and the discharge capacity at the 1st cycle. A high capacity retention rate was evaluated as having good cycle characteristics.
[0513] (Cycle Characteristics Evaluation 2)
[0514] The capacity retention rate (%) was calculated based on the following formula from the discharge capacity at the 300th cycle and the discharge capacity at the 1st cycle. A high capacity retention rate was evaluated as having good cycle characteristics.
[0515] Evaluation result (%) = (100 × retention capacity after 300 cycles / discharge capacity at the first cycle)
[0516] <Fusing / Melting (F / MD) Characteristics>
[0517] (i) 0.5 MPa pressure and 2°C / min heating rate
[0518] The positive electrode, separator and negative electrode are cut into a circular shape with a diameter of 200mm and stacked, and a non-aqueous electrolyte is added to the obtained stack to penetrate the whole. The stack is clamped in the center of a circular aluminum heater with a diameter of 600mm, and the aluminum heater is pressurized to 0.5MPa from the top and bottom with a hydraulic jack to complete the preparation for the measurement. While heating the above-mentioned stack with an aluminum heater at a heating rate of 2°C / min, the resistance (Ω) between the electrodes is measured. The temperature at which the separator is melted and the resistance between the electrodes rises and the resistance exceeds 1000Ω for the first time is taken as the shutdown temperature. In addition, the heating is further continued, and the temperature at which the resistance is reduced to below 1000Ω is taken as the melting temperature (film rupture temperature).
[0519] (ii) 10 MPa maximum pressure and 15°C / min heating rate
[0520] The positive electrode, separator and negative electrode are cut into a circular shape with a diameter of 200 mm, and a non-aqueous electrolyte is added to the stacked body to penetrate the whole body. The stack is clamped in the center of a circular aluminum heater with a diameter of 600 mm, and a hydraulic jack is used to apply pressure to the aluminum heater from the top and bottom to 10 MPa to complete the preparation for the measurement. While heating the stack with an aluminum heater at a heating rate of 15°C / min, the resistance (Ω) between the electrodes is measured. The temperature at which the resistance between the electrodes rises and the resistance exceeds 1000Ω for the first time is taken as the shutdown temperature (°C). In addition, the temperature at which the resistance is reduced to below 1000Ω by further heating is taken as the melting temperature (°C).
[0521] It should be noted that, for either evaluation (i) or (ii), a wire for measuring resistance was bonded to the back of the aluminum foil of the positive electrode produced by "1a. Production of positive electrode" in the above item <Battery destruction safety test 1> using a conductive silver paste. In addition, a wire for measuring resistance was bonded to the back of the copper foil of the negative electrode produced by "1b. Production of negative electrode" in the above item <Battery destruction safety test 1> using a conductive silver paste. Furthermore, the electrolyte-containing electrolyte prepared by "1c. Preparation of non-aqueous electrolyte" in the above item <Battery destruction safety test 1> was also used for the F / MD characteristic test.
[0522] <Safety test (nail penetration test) 2>
[0523] 2a. Preparation of positive electrode
[0524] The positive electrode active material is nickel, manganese, cobalt composite oxide (NMC) (Ni:Mn:Co = 1:1:1 (element ratio), density 4.70g / cm 3 ) 90.4 mass%, graphite powder (KS6) as a conductive additive (density 2.26 g / cm 3, number average particle size 6.5 μm) 1.6 mass% and acetylene black powder (AB) (density 1.95 g / cm 3 , number average particle size 48nm) 3.8% by mass, and PVDF (density 1.75g / cm 3 ) and 4.2 mass % were mixed and dispersed in NMP to prepare slurry. The slurry was coated on one side of an aluminum foil with a thickness of 20 μm constituting the positive electrode current collector using a die coater, dried at 130°C for 3 minutes, and then compression-molded using a roll press to produce a positive electrode. At this time, the amount of positive electrode active material coated was 109 g / m 2 .
[0525] 2b. Preparation of negative electrode
[0526] Graphite powder A (density 2.23 g / cm 3 , number average particle size 12.7 μm) 87.6 mass% and graphite powder B (density 2.27 g / cm 3 , number average particle size 6.5μm) 9.7% by mass, and 1.4% by mass (solid content conversion) of ammonium salt of carboxymethyl cellulose as a resin binder (solid content concentration 1.83% by mass aqueous solution) and 1.7% by mass of diene rubber latex (solid content conversion) (solid content concentration 40% by mass aqueous solution) are dispersed in purified water to prepare a slurry. The slurry is applied to one side of a copper foil with a thickness of 12μm constituting the negative electrode collector with a die coater, and after drying at 120°C for 3 minutes, compression molding is performed with a roller press to produce a negative electrode. At this time, the amount of negative electrode active material applied is 52g / m 2 .
[0527] 2c. Preparation of non-aqueous electrolyte
[0528] A non-aqueous electrolyte was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L.
[0529] 2d.Battery production
[0530] Using the positive electrode, negative electrode, non-aqueous electrolyte, and separator (separator of the embodiment or separator of the comparative example) obtained in the above 2a to 2c, a laminated secondary battery with a size of 100mm×60mm and a capacity of 3Ah was prepared, which was charged by constant current constant voltage (CCCV) for 3 hours under the conditions of a current value of 1A (0.3C) and a final battery voltage of 4.2V.
[0531] 2e. Nail evaluation
[0532] The laminated secondary battery was placed on an iron plate in an explosion-proof room with adjustable temperature. The temperature in the explosion-proof room was set to 40°C, and an iron nail with a diameter of 3.0 mm was passed through the center of the laminated secondary battery at a speed of 2 mm / sec, with the nail remaining in the state of penetration. The temperature of the thermocouple set inside the nail in such a way that the temperature inside the laminated battery can be measured after the nail penetrates was measured to evaluate whether there was ignition.
[0533] The evaluation was repeated using a laminated secondary battery newly produced in the same manner, and the number of samples in which ignition did not occur (non-ignition) was calculated as a % value according to the following formula.
[0534] Evaluation result (%) = (100 × number of samples without ignition / total number of samples)
[0535] <Extrusion stability>
[0536] The state of the extruded polyolefin composition was observed during the extrusion step and evaluated based on the following criteria.
[0537] A (good): The current value variation of the extruder is within ±0.5 A when the average value is taken for 300 seconds.
[0538] B (bad): The current value variation of the extruder exceeds ±0.5 A in the average value over 300 seconds.
[0539] <Metal Content>
[0540] The mass ratios of Sn atoms, Zn atoms, Ti atoms, Cu atoms, Fe atoms, Ni atoms, etc. contained in the sample were measured using an inductively coupled plasma (ICP) emission spectrometer.
[0541] <Experimental Group I>
[0542] [Method for producing silane grafted modified polyolefin]
[0543] The viscosity average molecular weight (Mv) of the raw material polyolefin used in the silane grafted modified polyolefin is 100,000 to 1,000,000, the weight average molecular weight (Mw) is 30,000 to 920,000, and the number average molecular weight can be 10,000 to 150,000, and can be propylene or butene copolymerized alpha olefin. While the raw material polyethylene is melt-kneaded by an extruder, an organic peroxide (di-tert-butyl peroxide) is added, and after free radicals are generated in the polymer chain of the alpha olefin, trimethoxyalkoxy-substituted vinyl silane is injected, and alkoxysilyl groups are introduced into the alpha olefin polymer through addition reaction to form a silane grafted structure. In addition, in order to simultaneously adjust the free radical concentration in the system, an antioxidant (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) is added in an appropriate amount to inhibit the chain reaction (gelation) in the alpha olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, pelletized, and then dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxy-substituted vinyl silane. The residual concentration of unreacted trimethoxyalkoxy-substituted vinyl silane in the pellets was about 10 to 1500 ppm.
[0544] The silane-graft-modified polyethylene obtained by the above-mentioned production method is represented as "silane-modified polyethylene (B)" in Tables 1 to 3.
[0545] [Film Production Example I]
[0546] (Sheet forming process)
[0547] To 79.2% by mass of polyethylene (polyethylene (A)) which is a homopolymer with a weight average molecular weight of 2,000,000, 19.8% by mass of silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR of 0.4 g / min obtained by modification reaction of a polyolefin with a viscosity average molecular weight of 20,000 as a raw material by trimethoxyalkoxy-substituted vinylsilane (according to which the resin compositions of (A) and (B) are 0.8 and 0.2, respectively) and 1% by mass of pentaerythritol-tetrakis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant were added and dry-mixed using a drum mixer to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder from a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity at 37.78°C 7.59×10 -5 m 2 / s) are injected into the extruder roller.
[0548] The mixture and liquid paraffin were melt-kneaded in an extruder, and the feeder and pump were adjusted so that the amount of liquid paraffin in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 230° C., a screw speed of 240 rpm, and a discharge of 18 kg / h.
[0549] Next, the melt-kneaded product was extruded through a T-die onto a cooling roll whose surface temperature was controlled to be 25° C. and cast, thereby obtaining a gel sheet (sheet-like molded product) having a green film thickness of 1400 μm.
[0550] (Stretching process)
[0551] Next, the gel sheet was introduced into a simultaneous biaxial stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD ratio 7.0 times, TD ratio 6.0 times (i.e. 7×6 times), and biaxial stretching temperature 125°C.
[0552] (Porous Body Forming Step)
[0553] Next, the stretched gel sheet is introduced into a methyl ethyl ketone bath, fully immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then dried to remove the methyl ethyl ketone, thereby obtaining a porous body.
[0554] (Heat treatment process)
[0555] Next, the porous body was introduced into a TD stenter for heat setting (HS), and HS was performed at a heat setting temperature of 125° C. and a stretching ratio of 1.8 times, and then a relaxation operation of 0.5 times in the TD direction was performed (ie, the HS relaxation ratio was 0.5 times).
[0556] (Affinity treatment process)
[0557] Furthermore, the heat-treated porous body was introduced into an ethanol bath (affinity treatment tank), immersed and allowed to remain there for 60 seconds, and affinity treatment of the heat-treated porous body was performed to obtain an affinity-treated porous body.
[0558] (Cross-linking treatment process)
[0559] Furthermore, the affinity-treated porous body was introduced into a 25% caustic soda aqueous solution (crosslinking treatment tank), immersed and allowed to remain there for 60 seconds to perform crosslinking treatment on the affinity-treated porous body, thereby obtaining a crosslinking-treated porous body.
[0560] (Washing and drying process)
[0561] The crosslinked porous body was then introduced into water (water washing tank) and immersed for 60 seconds to wash the crosslinked porous body, and then introduced into a conveyor dryer and dried at 120° C. for 60 seconds to obtain a microporous membrane.
[0562] Then, the end of the obtained microporous membrane was cut and wound into a mother roll having a width of 1,100 mm and a length of 5,000 m.
[0563] [Examples I-1 to I-11, Comparative Examples I-1 to I-4]
[0564] As shown in Tables 1 to 3, the same operation as in the above-mentioned Film Formation Example I was performed except that the quantitative ratio of components A and B and the crosslinking method / conditions were changed to obtain the microporous membranes shown in Tables 1 to 3. The obtained microporous membranes were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are also shown in Tables 1 to 3.
[0565] For the separator obtained in Example I-1, a TMA map was prepared ( Figure 1 ), heat release diagram of battery nail puncture safety test ( Figure 2 ) and voltage drop diagram ( Figure 3 ).
[0566] [Table 1]
[0567]
[0568] [Table 2]
[0569]
[0570] [Table 3]
[0571]
[0572] The term "resin composition" in Tables 1 to 3 indicates the ratio relative to the total amount of the silane graft-modified polyolefin and the polyethylene.
[0573] The term "method" in Tables 1 to 3 indicates the method of the silane crosslinking reaction, and is thus classified into a method based on an alkali treatment, an acid treatment, a hot water treatment, or a dehydration condensation catalyst.
[0574] The term "time point of cross-linking reaction" in Tables 1 to 3 indicates at which step of the above-described (1) sheet forming step, (2) stretching step, (3) porous body forming step, (4) heat treatment step, (5) affinity treatment step, (6) cross-linking treatment step, and (7) water washing and drying step the silane cross-linking reaction is carried out.
[0575] In Example I-4, a 10% hydrochloric acid solution was used instead of a 25% caustic soda aqueous solution, and in Comparative Example I-2, a 2.5 kg / m 2Furthermore, in Comparative Examples I-3 and I-4, the crosslinking reaction was carried out at the time points listed in Table 3, and the crosslinking treatment step was omitted.
[0576] In Example I-11, the water washing time was changed from 60 seconds to 10 minutes to adjust the amount of metal ions with respect to the above-mentioned production example.
[0577] The term "reagent" in Tables 1 to 3 means a reagent used in the cross-linking treatment step in the film forming example except for Comparative Examples I-3 and I-4.
[0578] The term "temperature" in Tables 1 to 3 means the temperature in the process described at the time point of the cross-linking reaction.
[0579] The terms "pH of the crosslinking treatment tank" and "pH of the water washing treatment tank" in Tables 1 to 3 indicate the pH in each tank. For example, "7 to 12" indicates that the pH has a wide distribution from the vicinity of the tank inlet to the vicinity of the tank outlet.
[0580] The "silane-modified polyethylene (B)" in Tables 1 to 3 has a density of 0.95 g / cm 3 A silane-modified polyethylene having a melt mass flow rate (MFR) at 190° C. of 0.4 g / min.
[0581] <Experimental Group II>
[0582] [Method for producing silane grafted modified polyolefin]
[0583] The viscosity average molecular weight (Mv) of the raw material polyolefin used in the silane grafted modified polyolefin is 100,000 to 1,000,000, the weight average molecular weight (Mw) is 30,000 to 920,000, and the number average molecular weight can be 10,000 to 150,000, and can be propylene or butene copolymerized alpha olefin. While the raw material polyethylene is melt-kneaded by an extruder, an organic peroxide (di-tert-butyl peroxide) is added to generate free radicals in the polymer chain of the alpha olefin, and then trimethoxyalkoxy-substituted vinyl silane is injected to introduce alkoxysilyl groups into the alpha olefin polymer through addition reaction to form a silane grafted structure. In addition, in order to simultaneously adjust the free radical concentration in the system, an antioxidant (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) is added in an appropriate amount to inhibit the chain reaction (gelation) in the alpha olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, pelletized, and then dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxy-substituted vinyl silane. The residual concentration of unreacted trimethoxyalkoxy-substituted vinyl silane in the pellets was about 10 to 1500 ppm.
[0584] The silane-grafted modified polyolefin obtained by the above-mentioned production method is represented as "silane-modified polyethylene (B)" in Tables 1 to 3. It should be noted that the density of the silane-grafted modified polyolefin used this time is 0.94 g / cm 3 And the MFR is 0.65 g / min.
[0585] [Film Formation and Coating Example II]
[0586] (Formation of Microporous Film)
[0587] To 79.2 wt % of polyethylene (polyethylene (A)) which is a homopolymer with a weight average molecular weight of 500,000, 19.8 wt % of silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR (190° C.) of 0.4 g / min obtained by modification reaction of a polyolefin with a viscosity average molecular weight of 20,000 as a raw material by trimethoxyalkoxy-substituted vinylsilane (according to which the resin compositions of (A) and (B) are 80% and 20%) and 1 wt % of pentaerythritol-tetrakis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant were added and dry-mixed using a drum mixer to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder from a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity at 37.78° C. 7.59×10 -5 m 2 / s) are injected into the extruder roller.
[0588] The mixture and liquid paraffin were melt-mixed in an extruder, and the feeder and pump were adjusted so that the amount of liquid paraffin in the extruded polyolefin composition was 70% by weight (i.e., the polymer concentration was 30% by weight). The melt-mixing conditions were a set temperature of 220° C., a screw speed of 240 rpm, and a discharge of 18 kg / h.
[0589] Next, the melt-kneaded product was extruded through a T-die onto a cooling roll whose surface temperature was controlled to be 25° C. and cast, thereby obtaining a gel sheet (sheet-like molded product) having a green film thickness of 1400 μm.
[0590] Next, the sheet-like molded body was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD ratio 7.0 times, TD ratio 6.0 times (i.e. 7×6 times), and biaxial stretching temperature 125°C.
[0591] Next, the stretched gel sheet is introduced into a methyl ethyl ketone bath, fully immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then dried to remove the methyl ethyl ketone, thereby obtaining a porous body.
[0592] Next, the porous body was introduced into a TD stenter for heat setting (HS), and HS was performed at a heat setting temperature of 125° C. and a stretching ratio of 1.8 times, and then a relaxation operation of 0.5 times in the TD direction (i.e., HS relaxation ratio of 0.5 times) was performed to obtain a microporous membrane.
[0593] Then, the end of the obtained microporous membrane was cut and wound up into a microporous membrane mother roll having a width of 1,100 mm and a length of 5,000 m.
[0594] (Method for producing acrylic latex)
[0595] The acrylic latex used as the resin binder can be produced by the following method.
[0596] Into a reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank, and a thermometer, 70.4 parts by mass of ion exchange water, as well as 0.5 parts by mass of "Aquaron KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Co., Ltd.) as emulsifiers were added. Next, the temperature inside the reaction vessel was raised to 80° C., and 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate was added while maintaining the temperature at 80° C. to obtain an initial mixture. Five minutes after the addition of the ammonium persulfate aqueous solution was completed, the emulsion was dropped from the dropping tank into the reaction vessel over 150 minutes.
[0597] It should be noted that the above-mentioned emulsion was prepared by mixing the following substances for 5 minutes using a homomixer: 70 parts by mass of butyl acrylate; 29 parts by mass of methyl methacrylate; 1 part by mass of methacrylic acid; 3 parts by mass of "Aquaron KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 3 parts by mass of "ADEKA REASOAPSR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Co., Ltd.) as emulsifiers; 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate; and a mixture of 52 parts by mass of ion-exchanged water.
[0598] After the dropwise addition of the emulsion was completed, the temperature inside the reaction vessel was maintained at 80°C for 90 minutes, and then cooled to room temperature. The obtained emulsion was adjusted to pH = 8.0 with a 25% aqueous ammonium hydroxide solution, and a small amount of water was added to obtain an acrylic latex with a solid content of 40%. The obtained acrylic latex had a number average particle size of 145 nm and a glass transition temperature of -23°C.
[0599] (Formation of Inorganic Porous Layer)
[0600] 95 parts by weight of aluminum hydroxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by weight (solid content conversion) of polycarboxylic acid ammonium aqueous solution (SN Dispersant 5468 manufactured by SAN NOPCO LIMITED, solid content concentration 40%) as an ionic dispersant are uniformly dispersed in 100 parts by weight of water to prepare a dispersion. The obtained dispersion is crushed using a bead mill (tank volume 200 cc, zirconia bead diameter 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm. 4.6 parts by weight (solid content conversion) of acrylic latex (solid content concentration 40%, average particle size 145 nm, glass transition temperature -23°C, constituent monomers: butyl acrylate, methyl methacrylate, methacrylic acid) as a resin binder are added to prepare a slurry containing inorganic particles.
[0601] Next, the microporous membrane is continuously unrolled from the microporous membrane mother roll, and a slurry containing inorganic particles is coated on one side of the microporous membrane using a gravure reverse coater, followed by drying in a drier at 60° C. to remove water, and then winding up to obtain a separator mother roll.
[0602] During the evaluation, the separators unwound from the mother roll were cut as necessary and used as separators for evaluation.
[0603] [Examples II-1 to II-2, Comparative Example II-2]
[0604] Microporous membranes shown in Tables 1 to 3 were obtained by performing the same operations as in Membrane Formation and Coating Example II except that the ratio of components A to B, the presence or composition of the inorganic layer, and the crosslinking method and conditions were changed as described in Tables 1 to 3.
[0605] It should be noted that in Example II-1, the microporous membrane was introduced into a 25% caustic soda aqueous solution (temperature 80°C, pH 8.5-14), and in Example II-2, the microporous membrane was introduced into a 10% hydrochloric acid aqueous solution (temperature 60°C, pH 1-6.5), and immersed and left for 60 seconds to form an inorganic porous layer after cross-linking treatment of the microporous membrane.
[0606] [Comparative Example II-1]
[0607] To 79.2 wt % of polyethylene (polyethylene (A)) which is a homopolymer with a weight average molecular weight of 500,000, 19.8 wt % of silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR (190° C.) of 0.4 g / min obtained by modification reaction of a polyolefin with a viscosity average molecular weight of 20,000 as a raw material by trimethoxyalkoxy-substituted vinylsilane (according to which the resin compositions of (A) and (B) are 80% and 20%, respectively) and 1 wt % of pentaerythritol-tetrakis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant were added and dry-mixed using a drum mixer to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder from a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity at 37.78° C. 7.59×10 -5 m 2 / s) are injected into the extruder roller.
[0608] The mixture and liquid paraffin were melt-mixed in an extruder, and the feeder and pump were adjusted so that the amount of liquid paraffin in the extruded polyolefin composition was 70% by weight (i.e., the polymer concentration was 30% by weight). The melt-mixing conditions were a set temperature of 220° C., a screw speed of 240 rpm, and a discharge of 18 kg / h.
[0609] Next, the melt-kneaded product was extruded through a T-die onto a cooling roll whose surface temperature was controlled to be 25° C. and cast, thereby obtaining a gel sheet (sheet-like molded product) having a green film thickness of 1400 μm.
[0610] Next, the sheet-like molded body was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD ratio 7.0 times, TD ratio 6.0 times (i.e. 7×6 times), and biaxial stretching temperature 125°C.
[0611] Next, the stretched gel sheet is introduced into a methyl ethyl ketone bath, fully immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then dried to remove the methyl ethyl ketone, thereby obtaining a porous body.
[0612] Next, the porous body was introduced into a TD stenter for heat setting (HS), and HS was performed at a heat setting temperature of 125° C. and a stretching ratio of 1.8 times, and then a relaxation operation of 0.5 times in the TD direction was performed (ie, the HS relaxation ratio was 0.5 times).
[0613] In Comparative Example 1, in order to use the heat-treated porous body as a separator, the end of the obtained porous body was cut and wound into a mother roll having a width of 1,100 mm and a length of 5,000 m.
[0614] Next, the heat-treated porous body obtained above is guided into an ethanol bath (affinity treatment tank), immersed and left for 60 seconds to perform affinity treatment on the heat-treated porous body, thereby obtaining an affinity-treated porous body.
[0615] Next, the affinity-treated porous body is guided into a 25% aqueous sodium hydroxide solution (temperature: 80°C, pH: 8.5 - 14), immersed and left for 60 seconds to perform crosslinking treatment on the affinity-treated porous body, thereby obtaining a crosslinked porous body.
[0616] Next, the crosslinked porous body is guided into water (water washing treatment tank), immersed and left for 60 seconds to wash the crosslinked porous body. Then it is guided into a conveyor dryer and dried under the conditions of 120°C for 60 seconds to obtain a microporous membrane.
[0617] Then, for the obtained microporous membrane, the ends are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[0618] For Comparative Example II-1, during the above evaluation, the microporous membrane unwound from the master roll is slit as needed and used as a separator for evaluation.
[0619] [Evaluation Results]
[0620] For the microporous membranes and batteries obtained in Examples II-1 to II-2 and Comparative Examples II-1 to II-2, various evaluations are carried out in accordance with the above evaluation method, and the evaluation results are also shown in Table 4.
[0621] [Table 4]
[0622]
[0623] <Experimental Group III>
[0624] [Example III-1]
[0625] <Fabrication of A Layer>
[0626] (Fabrication of Silane-Grafted Modified Polyolefin)
[0627] Polyethylene with a viscosity average molecular weight of 100,000 is used as the raw material polyethylene. While the raw material polyethylene is melt-kneaded by an extruder, an organic peroxide (di-tert-butyl peroxide) is added. After free radicals are generated in the polymer chain of α-olefin, trimethoxyalkoxy-substituted vinyl silane is injected, and alkoxysilyl groups are introduced into the α-olefin polymer through addition reaction to form a silane grafted structure. In addition, in order to simultaneously adjust the free radical concentration in the reaction system, an antioxidant (pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) is added in an appropriate amount to inhibit the chain reaction (gelation) in α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water, pelletized, and then heated and dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkoxy-substituted vinyl silane. It should be noted that the residual concentration of unreacted trimethoxyalkoxy-substituted vinyl silane in the pellets is about 1500ppm or less.
[0628] By the modification reaction using the trimethoxyalkoxy-substituted vinylsilane as described above, a silane-modified polyethylene having an MFR (190° C.) of 0.4 g / min was obtained.
[0629] (Production of Layer A)
[0630] 35% by mass of the silane-modified polyethylene obtained above was blended into 65% by mass of polyethylene of a homopolymer having a weight average molecular weight of 700,000 to form a resin compound, 1% by mass of pentaerythritol-tetrakis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant was added to the compound, and dry blending was performed using a drum mixer to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder from a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity 7.59×10 at 37.78°C) was added by a plunger pump. -5 m 2 / s) are injected into the extruder roller.
[0631] The mixture and liquid paraffin were melt-kneaded in an extruder, and the feeder and pump were adjusted so that the amount of liquid paraffin in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220° C., a screw speed of 240 rpm, and a discharge of 18 kg / hour. Next, the melt-kneaded product was extruded through a T-die onto a cooling roller whose surface temperature was controlled to 25° C. and cast, thereby obtaining a gel sheet (sheet-shaped molded body) with a film thickness of 1400 μm.
[0632] Next, the sheet-like molded body was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD ratio 7.0 times, TD ratio 6.0 times (i.e. 7×6 times), and biaxial stretching temperature 123°C.
[0633] Next, the stretched gel sheet is guided to a methylene chloride bath, fully impregnated in methylene chloride to extract and remove liquid paraffin, and then dried to remove methylene chloride, obtaining a porous body.
[0634] Next, in order to perform heat setting (HS), the porous body is guided to a TD tenter, and heat setting and relaxation operations are performed. The heat setting conditions input to the TD tenter are to perform HS at a heat setting temperature of 132 °C and a draw ratio of 2.1 times, and then, perform a relaxation operation to 1.9 times of TD, obtaining a microporous membrane.
[0635] Then, for the obtained microporous membrane, the ends are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[0636] At the above evaluation, the microporous membrane unwound from the master roll is slit as needed and used as the evaluation A layer.
[0637] For the obtained evaluation A layer, the film thickness, air permeability, porosity, etc. are measured and shown in Table 5.
[0638] <Fabrication of B layer>
[0639] 95 parts by mass of aluminum hydroxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by mass (in terms of solid content) of an aqueous ammonium polycarboxylate solution (SNDispersant 5468 manufactured by SAN NOPCO LIMITED, solid content concentration 40%) as an ionic dispersant are uniformly dispersed in 100 parts by mass of water to prepare a dispersion. The obtained dispersion is subjected to a crushing treatment with a bead mill (tank volume 200 cc, zirconia beads with a diameter of 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm, and a slurry containing inorganic particles is produced.
[0640] Next, the microporous membrane is continuously unwound from the above microporous membrane master roll, and the slurry containing inorganic particles is coated on one side of the microporous membrane with a gravure reverse coater, and then dried with a dryer at 60 °C to remove water and wound up to obtain a master roll of the separator.
[0641] At the evaluation, the separator unwound from the master roll is slit as needed and used as the evaluation separator.
[0642] [Examples III-2 to III-14 and Comparative Examples III-1 to III-2]
[0643] Taking the physical property values recorded in Table 5 as the target, the weight average molecular weight of the polyethylene of the homopolymer is changed, and at least any one of the stretching conditions, heat setting conditions, and relaxation operation conditions is set. In addition, the composition of the B layer is changed as shown in the record of Table 5.
[0644] Except for these changes, the separator was produced in the same manner as in Example III-1, and the above evaluation was performed using the obtained separator. The evaluation results are shown in Table 5.
[0645] [Table 5]
[0646]
[0647] <Experimental Group IV>
[0648] [Example IV-1]
[0649] <Production of Layer A>
[0650] (Production of Silane-Grafted Modified Polyolefin)
[0651] Using polyethylene with a viscosity-average molecular weight of 100,000 as the raw material polyethylene, while melt-kneading the raw material polyethylene with an extruder, an organic peroxide (di-tert-butyl peroxide) was added. After generating free radicals in the polymer chain of the α-olefin, trimethoxyalkoxysubstituted vinylsilane was injected, and an alkoxysilyl group was introduced into the α-olefin polymer through an addition reaction to form a silane-grafted structure. In addition, in order to simultaneously adjust the free radical concentration in the reaction system, an antioxidant (pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) was added in an appropriate amount to inhibit the chain-like chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, pelletized, and then heated and dried at 80 °C for 2 days to remove moisture or unreacted trimethoxyalkoxysubstituted vinylsilane. It should be noted that the residual concentration of unreacted trimethoxyalkoxysubstituted vinylsilane in the pellets is about 1500 ppm or less.
[0652] Through the modification reaction using trimethoxyalkoxysubstituted vinylsilane as described above, silane-modified polyethylene with an MFR (190 °C) of 0.4 g / min was obtained.
[0653] (Production of Layer A)
[0654] 35% by mass of the above-obtained silane-modified polyethylene was compounded with 65% by mass of a homopolymer polyethylene having a weight-average molecular weight of 750,000 to form a resin blend. 1% by mass of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant was added to the blend, and dry blending was performed using a drum mixer to obtain a mixture. The obtained mixture was fed into a twin-screw extruder by a feeder under a nitrogen atmosphere. In addition, liquid paraffin (kinematic viscosity at 37.78 °C is 7.59×10 -5 m 2 / s) injection extrusion machine drum.
[0655] In the extruder, the mixture and liquid paraffin are melt-kneaded. The feeder and pump are adjusted so that the amount of liquid paraffin in the extruded polyolefin composition is 70% by mass (i.e., the polymer concentration is 30% by mass). The melt-kneading conditions are a set temperature of 220 °C, a screw speed of 240 rpm, and a discharge rate of 18 kg / hour. Then, the melt-kneaded material is extruded through a T-die onto a cooling roll with a surface temperature controlled at 25 °C and cast, thereby obtaining a gel sheet (sheet-shaped molded body) with a blank film thickness of 1280 μm.
[0656] Next, the sheet-shaped molded body is guided to a simultaneous biaxial stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions are set to an MD magnification of 7.0 times, a TD magnification of 6.5 times (i.e., 7×6.5 times), and a biaxial stretching temperature of 125 °C.
[0657] Next, the stretched gel sheet is guided to a dichloromethane bath, fully impregnated in dichloromethane to extract and remove the liquid paraffin, and then dried to remove dichloromethane, obtaining a porous body.
[0658] Next, in order to perform heat setting (HS), the porous body is guided to a TD stretching machine, and HS is performed at a heat setting temperature of 131 °C and a stretching ratio of 1.9 times. Then, a relaxation operation is performed to a TD of 1.7 times, obtaining a microporous membrane.
[0659] Then, for the obtained microporous membrane, the ends are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[0660] During the above evaluation, the microporous membrane unwound from the master roll is slit as needed and used as the evaluation A layer.
[0661] For the obtained evaluation A layer, the film thickness, air permeability, porosity, etc. are measured and shown in Table 6.
[0662] <Fabrication of B layer>
[0663] 95 parts by mass of aluminum hydroxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by mass (in terms of solid content) of an aqueous ammonium polycarboxylate solution (SNDispersant 5468 manufactured by SAN NOPCO LIMITED, solid content concentration 40%) as an ionic dispersant are uniformly dispersed in 100 parts by mass of water to prepare a dispersion. The obtained dispersion is subjected to a crushing treatment using a bead mill (tank volume 200 cc, zirconia beads with a diameter of 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm, and a slurry containing inorganic particles is fabricated.
[0664] Next, the microporous membrane is continuously unwound from the above-mentioned master roll of the microporous membrane, and a slurry containing inorganic particles is coated on one side of the microporous membrane using a gravure reverse coater. Then, it is dried with a dryer at 60°C to remove water, and wound up to obtain a master roll of the separator.
[0665] At the time of evaluation, the separator unwound from the master roll is slit as needed and used as the separator for evaluation.
[0666] [Examples IV-2 to IV-3 and Comparative Examples IV-1 to IV-2]
[0667] Taking the physical property values described in Table 6 as the target, the weight average molecular weight of the polyethylene of the homopolymer is changed, and at least any one of the stretching conditions, heat setting conditions, and relaxation operation conditions is set. In addition, the composition of the B layer is changed as described in Table 6.
[0668] Except for these changes, the separator is produced by the same method as in Example IV-1, and the above evaluation is performed using the obtained separator. The evaluation results are shown in Table 6.
[0669] [Table 6]
[0670]
[0671] <Experimental Group V>
[0672] Porous membranes are formed in the same manner as in Examples 1 to 3 and Comparative Examples 2 to 3 given in Patent Document 5 (Japanese Unexamined Patent Application Publication No. 2001-176484), and are respectively designated as porous membranes V-1 to V-5. For the porous membranes V-1 to V-5, the gel fraction (%), heat resistance temperature (°C), and needle penetration strength (gf / 25 μm) are evaluated according to the method described in Patent Document 5, and further, the TMA film breakage temperature under load is measured in accordance with the above item <TMA film breakage temperature> of this specification. The results are shown in Table 7.
[0673] [Table 7]
[0674]
[0675] The following points can be clarified from Table 7.
[0676] (a) Since the heat resistance temperature described in Patent Document 5 is the measurement temperature under the condition of no load applied, it is not the TMA film breakage temperature described in the first, second, and third embodiments of the present invention.
[0677] (b) As shown in Examples 1 to 3 and Comparative Examples 2 to 3 of Patent Document 5, for porous membranes V-1 to V-5 that were crosslinked under the conditions of a temperature of 90°C, a humidity of 95%, and 4 hours, if the TMA film-breaking temperature is measured under the conditions of the above item <TMA film-breaking temperature> in this specification, the TMA film-breaking temperature will be less than 180°C.
Claims
1. A separator for a power storage device, wherein the shutdown temperature measured based on the resistance under a pressure of 10.0 MPa is 130° C. to 160° C. and the melting temperature is 200° C. or higher, the separator comprising a first porous layer containing a silane-modified polyolefin and having a cross-linked structure, wherein the heat shrinkage rate (T2) at 150° C. after the cross-linked structure is formed in the first porous layer is 0.02 times or more and 0.7 times or less of the heat shrinkage rate (T1) at 150° C. before the cross-linked structure is formed, and the manufacturing method of the separator for a power storage device comprises the following steps: (1) a sheet forming step, in which the silane grafted modified polyolefin, polyethylene and plasticizer are extruded into a sheet by an extruder, cooled and solidified, and processed into a sheet-shaped body; (2) a stretching step of biaxially stretching the sheet-like formed body at a surface ratio of 20 to 250 times to form a stretched product; (3) a porous body forming step of extracting the plasticizer from the stretched product to form a porous body; (4) a heat treatment step of subjecting the porous body to heat treatment, stretching and relaxing the porous body in the width direction, and obtaining a heat-treated porous body; (5) an affinity treatment step of immersing the heat-treated porous body in an organic solvent having amphiphilicity to water and organic matter to increase the affinity of the heat-treated porous body with the liquid, thereby obtaining an affinity-treated porous body having the organic solvent immersed therein; (6) a cross-linking treatment step, wherein the affinity-treated porous body is contacted with a mixture containing an organic metal catalyst and water, or the affinity-treated porous body is immersed in an alkaline solution or an acid solution to perform a silane dehydration condensation reaction to form oligosiloxane bonds, thereby obtaining a cross-linked porous body; (7) a water washing and drying step of washing and drying the cross-linked porous body to obtain a microporous membrane comprising the silane-modified polyolefin; as well as (8A) A coating step of forming an inorganic porous layer including inorganic particles and a resin binder on at least one surface of the microporous membrane. 2 . An electricity storage device comprising an electrode, the separator for an electricity storage device according to claim 1 , and a non-aqueous electrolyte.
Citation Information
Patent Citations
Porous membrane, battery separator comprising porous membrane, and manufacture thereof
JP1999144700A
Porous film, battery separator comprising porous film, and its production
JP1999172036A
Production of microporous resin film
JP2000319441A
Porous film
JP2001176484A
Separator for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2007299612A